Efficient recovery of tin from fine-grained tin tailings via a combined centrifugal and suspended vibrating cone process - Jianjun Sun; Rong Peng; Dianwen Liu; Mingrui Liu; Peilun Shen; Tianfu Zhang; Liuyang Dong; Yuqiang Mao (Minerals Engineering, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Magnetic biochar as dual-functional mediator for low-field magnetic separation of vivianite and membrane fouling mitigation in anaerobic membrane bioreactors - Feng-Ai Yang; Ying Dong; Jifei Chang; Rong Chen; Xin Wang; Juncheng Liu; Fernanda Leite Lobo; Devard I. Stom; Nan Li (Bioresource Technology, 2026)

An ethylene-responsive element with spatial bias in Arabidopsis - Junchi Ma; Caiyi Dong; Rong Yu; Xiaoting Qi (Molecular Biology Reports, 2026)

Exploration of shared gene signatures and molecular mechanisms between psoriasis and COVID-19: evidence from transcriptome data - Rong-Jing Dong; Lu-Hui Yang; Yu-Ye Li; You-Wang Lu (Mammalian Genome, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Oral Janus nanomotor covalent conjugation rapeseed protein-derived DPP-IV inhibitory peptide and liraglutide: A self-propelled targeted delivery system for promoting insulin secretion and glucose-lowering - Huimin Dong; Haiyan He; Huizhen Xing; Chengzhi Guo; Zhigao Wang; Rong He (Food Research International, 2026)

Unlocking dual-site regulation in perovskite-modified separators for efficient polysulfide conversion in lithium-sulfur batteries - Mingxu Li; Byeong hun Oh; Heejin Kim; Dong-Ho Baek; Ying Liu; Dengzhou Liu; Zabrian Dirfan; SuHyeon Ahn; Rong Yang; Jou-Hyeon Ahn; Inseok Seo; Du-Hyun Lim; et al. (Chemical Engineering Journal, 2026)

Mechanistic characterization of the discrepancies in enrichment of nitrate between agricultural and urban-industrial rivers in the semi-arid areas of northern China: Insights from multi-element stable isotope analysis - Ang Dong; Yu Liu; Guiqi Liu; Guangzhi Rong; Shuaihao Liu; Mingjun Mo; Haixia Wang; Guoguang Wang (Journal of Hydrology, 2026)

Insights into performance and mechanism of VS2@Fe3O4 magnetic nano-composite as heterogeneous catalyst of peroxymonosulfate for phthalate esters degradation - Xue Rong; Hongying Wang; Jing Chang; Zhongpeng Wang; Qigang Gao; Yanhao Wang; Dong Ma (Journal of Environmental Chemical Engineering, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Conjugation-enhanced crown ether-based polymer for “locking-controlled” recognition and confined space synergistic co-capture of Sr(II) and U(VI) - Qi-Dong Ye; Jie Wang; Yang Li; Yang Wang; Zi-Hao Feng; Dong-Qing Huang; Yun Wang; Shuang Yang; Rong Hua (Desalination, 2026)

Viper-inspired vigilance: A biomimetic PPy@M(OH)(OCH3) (M = Co, Ni) smart armor endows cotton with high-efficient fire-resistance, graded fire-alarming, and identification for firefighting postures - Caiyu Rong; Xiang Dong; Shidai Zhang; Shuqin Ding; Zhaoxin Zhang; Yan Ma; Zixin Lin; Yuhe Song; Jiayi Zhang; Shibin Nie; Konghu Tian (Chemical Engineering Journal, 2026)

Knockout of Resilin-like genes results in diminished wing size in silkworm moths - Tingting Tian; Chunxia Xiao; Haonan Dong; Qinglang Wang; Jia Fang; Zhonghui Dong; Yiran Zhu; Qingyu Rong; Yong Hou (Journal of Insect Physiology, 2026)

Role of macrophage NLRP3 inflammasome activation in real-ambient particulate matter-induced abnormal hepatic glucose metabolism - Dong Wu; Zhen Zhang; Sixin Chen; Haoran Chen; Daochuan Li; Shuxin Zhang; Junjie Dou; Yuanyuan Ma; Rong Zhang; Lianhua Cui (Journal of Environmental Sciences, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Electrostatic-field-driven synergistic regulation of molecular conformation and mesostructure enables stable Na+ transport in 12 μm PVDF-HFP-based electrolytes - Jiaze Li; Rong Yang; Xiaobin Li; Aoyi Jiang; Xin Dong; Hongyu Shang; Yinglin Yan; Hyun Woo Kim; Jou-Hyeon Ahn (Chemical Engineering Journal, 2026)

In-situ generation and activation of H2O2 by synergistic dipole moment and multi-metal cycle for piezo-photocatalytic water cleanup - Zheng-Tao Dong; Long Sui; You Wu; Xiao-Ju Wen; Ya-Ya Yang; Yan-Rong Chen; Wen-Jun Wang; Hai Guo (Chemical Engineering Journal, 2026)

Role of pyroptosis in melanoma: Molecular mechanisms and therapeutic potentials - Xiao-Han Zhang; Ke Zhang; Xue-Chun Qu; Jing Zhang; Umm E. Laila; Bo Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2026)

Morphology and Phylogeny of Hyalinostachys dehongensis sp. nov., a Bambusicolous Species From Yunnan Province, China - Yu‐Rong Yan; Li‐Su Han; Gang‐Ya Xu; Samantha C. Karunarathna; Nakarin Suwannarach; Jaturong Kumla; A. N. W. Sumedha Thushari; Sajad Ali; Dong‐Qin Dai; Saowaluck Tibpromma (New Zealand Journal of Botany, 2026)
China has abundant bamboo resources, among which Yunnan Province is one of the regions with the greatest number of species. The unique natural and geographic advantages provide an excellent environment for fungal growth. This study collected and isolated saprobic hyphomycetes associated with dead bamboo in Yunnan Province, China. Based on detailed morphological comparisons and multi‐locus phylogenetic analyses of combined LSU, ITS, tef 1‐ α , rpb 2, tub 2, and cmdA sequence data, the new isolates are introduced here as a novel species, Hyalinostachys dehongensis in the family Stachybotryaceae of Ascomycota. A complete description, morphological illustrations, and phylogenetic analysis results for the new species are provided. In addition, this species is introduced here as the second species since this genus was introduced in 2020.

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Metabolic rewiring of Phanerochaete chrysosporium to enhance tolerance and degradation of aged polystyrene microplastics: Pyruvate metabolism and actin polarization - Yongkang Wu; Zelin Hou; Yin Lu; Rong Cai; Jiawei Huang; Yu Mao; Ningjia Dong; Hong Liang; Dawen Gao (Journal of Hazardous Materials, 2026)

Ultraviolet irradiation restores anammox sludge activity from sulfamethazine inhibition by activating energy reallocation and metabolic pathway shifts - Jin-Luo Pang; Rong-Rong Chang; Kai-Yue Dong; Bao-Cheng Huang; Ren-Cun Jin (Journal of Environmental Sciences, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Divergent controls on particulate and mineral-associated organic carbon in tropical forests of southern China - Dong Qiao; Licong Dai; Meihua Yang; Yue Jiao; Qiaoyan Chen; Rong Shang; Zhongmin Hu (Plant and Soil, 2026)

Shifts in microbial nutrient limitation drive microbial necromass carbon accumulation in mixed temperate plantations - Guohua Rong; Fan Du; Ying Zhang; Yaqi Dong; Hongyu Wu (Plant and Soil, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Impacts of trunk height, tree planting density, and wall heating on flow and pollutant dispersion inside an urban street canyon - Yuan-Dong Huang; Yan-Jiao Jiang; Rong Ji; Ke-Xin Wang; Meng-Xin Chai; Yang Luo; Peng-Yi Cui (Environmental Fluid Mechanics, 2026)

Single-cell omics in plants: technological advances and biological insights - Yi Chen; Yige Dong; Jindi Yang; Zhe Liu; Shengyu Rong; Qiulei Lang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

A 1D stepped coordination polymer based on Cu4I4 units for X-ray imaging over a broad temperature range - Ji-Hui Jia; Xiang-Long Hu; Dong Liang; Qianting Wang; Rong Zhang; Can-Zhong Lu (Chemical Engineering Journal, 2026)

Molecularly integrated dynamic chitosan network with topology-adaptive glucose/ROS responsiveness for coupled drug release and immunoregulation - Yuxiang Li; Sheng Dong; Ran Yu; Runjie Liu; Hengxi Xu; Hainuo Li; Wenbo Ming; Guochao Liao; Rong Zhang; Zhongqiu Liu; Wenxian Wang; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Bile acid-induced TBG depletion promotes trophoblast apoptosis via local thyroxine insufficiency in intrahepatic cholestasis of pregnancy - Gaoying Wang; Wen Hu; Jianyi Gao; Rong Wang; Ting Zhang; Ruirui Dong (Molecular and Cellular Biochemistry, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Unraveling the flame retardant mechanism of protein-rich matrix recovered from anaerobic sludge: The governing role of microstructural characteristics - Bo Zhang; Gaojun Wang; Yinghong Dong; Qian Li; Yu-You Li; Rong Chen (Water Research, 2026)

Bioaerosol multi-pollutant source localization in urban microclimates using an improved particle swarm optimization method with restricted search capabilities - Zhijian Liu; Yixiang Ma; Chenxing Hu; Haiyang Liu; Hongliang Zhang; Xin Li; Zhenhai Sun; Rui Rong; Zhijian Dong; Xiang Zhao; Guangpeng Yao (Sustainable Cities and Society, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Three undescribed terpenoids from the aerial parts of Alstonia scholaris - Bing-ru Liu; Chun-xiang Xu; Dan Liu; Yue Feng; Rong-tao Li; Jin-dong Zhong (Phytochemistry Letters, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Diversity and taxonomic revision of Hoya (Apocynaceae, Asclepiadoideae) in China based on morphological and molecular evidence - Yang Liu; Wang Xi; Nie-Rong Lu; Ji-Dong Ya; Jing-Feng Zhang; Lei Cai (Plant Systematics and Evolution, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

A colorimetric/fluorescent/electrochemical tri-modal biosensor based on dual CRISPR/Cas12a system for detection of microRNA - Hehua Zhang; Huan Zhu; Hongmin Gao; Yang Zhou; Longbin Que; Shengzhong Rong; Hongkun Ma; Dong Chang; Hongzhi Pan (Analytica Chimica Acta, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

When city lights turn blue: Spectral ALAN exposure, LED lighting, and diabetes prevalence using SDGSAT-1 - Yanqing Xu; Ruoyu Dong; Tingting Li; Sujin Zhang; Yan Liu; Yuchen Li; Kenan Li; Xiaobo Feng; Shuang Rong (Environmental Pollution, 2026)

Sensitivity analysis and multi-objective particle swarm optimization (MOPSO) of a hollow fiber membrane module for the solar-based heating and humidification system - Si Zeng; Peng Peng; Nan-Feng Li; Cai-Hang Liang; Rong-Hui Qi; Yan-fang Dong; Yu-Kui Men; Jia-Hui Li; Gui-Yin Li (Energy and Buildings, 2026)

Fe-regulated AnMBR for carbon & phosphorus co-recovery and membrane fouling control - Ying Dong; Rong Chen; Jifei Chang; Fengai Yang; Zhen Lei; Xin Wang; Nan Li (Chemical Engineering Journal, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Is ecological quality of river-connected lake basin higher than disconnected lake basins in the lower reaches of the Yangtze River, China? - Dong-zheng Yu; Ying Huang; Jing-wei Yang; Xiang-rong Song; Xin-sheng Chen (Environmental Monitoring and Assessment, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Antifungal mechanisms of Bacillus velezensis Shannan.BV80-12 extracellular metabolites against the citrus postharvest pathogen Penicillium italicum - Rong Wang; Yali Tan; Feiyan Dong; Jiao Yang; Xiao Li; Tong Gu; Jialan Zhang; Li Li; Mengxiang Gao (Postharvest Biology and Technology, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Local electric field regulation induces specific catalysis to achieve efficient and selective sensing of methanol - Cundong Feng; Shizhu Ling; Rong Tan; Weian Du; Xueqin Ouyang; Jianjun Xiong; Yangfeng Li; Haoyang Ren; Yingpu Wang; Weifang Liao; Qian Xiao; Wentao Dong; et al. (Chemical Engineering Journal, 2026)

Hierarchical Cu Ni micro-nanocone arrays as stable lithium metal hosts - Qiulong Tang; Guang Jiang; Jilu Zhao; Qingyu Dong; Jingshu Wang; Haiyang Zhang; Jianxin Ou; Xuechun Wang; Rong Huang; Hui Shao; Jun Ge; Xuefeng Gao; et al. (Chemical Engineering Journal, 2026)

Calcium-mediated modulation of ultra-low-ester pectin-gluten interactions: subunit-level mechanisms revealed using HMW-GS deletion lines and molecular dynamics simulations - Rong-ran Zhang; Ping-ping Zhang; Tian Lv; Bo Wang; Zhe Liu; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Carbohydrate Polymers, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Current trend on preparation, properties, and wound healing applications of polysaccharide-based hydrogel patches: A review - Jiaqi Tan; Rong Dong; Ruoshi Zhang; Xiaojun Liao; Hongkun Xue (Carbohydrate Polymers, 2026)

Chemical constituents from the twigs and leaves of Viburnum utile Hemsl. (Adoxaceae) and their taxonomic distribution - Dong-Mei Zhou; Lijin Jiao; Huai-Qin Liu; Bang-Quan Tang; Guo-Bo Xu; Qin-Feng Zhu; Xi-Rong Luo; Shang-Gao Liao; Ling-Ling Yu (Biochemical Systematics and Ecology, 2026)

Effects of different light regimes on the endogenous rhythm of Manila clam, Ruditapes philippinarum - Rong Gao; Zhiguo Dong; Yaoran Fan; Tao Wei; Baojun Tang; Hanfeng Zheng (Aquaculture, 2026)

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

Applying semi-supervised learning algorithms in real-environment solid waste classification - Dong–Ying Lan; Pin–Jing He; Hui–Huang Zou; Rong–Rong Kan; Yi Wang; Fan Lü; Hua Zhang (Resources, Conservation and Recycling, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Legacy perfluoroalkyl acids and emerging perfluoroalkyl ether carboxylic acids in the atmosphere of Laizhou Bay estuaries: Occurrence, gas–particle partitioning, and potential sources - Hao Sun; Xinchen Miao; Fengfeng Dong; Rong Sun; Xuan Jia; Xing Liu; Zilan Wu; Ziwei Yao; Jiayin Dai; Jianhui Tang; Jianmin Chen; Yitao Pan (Marine Environmental Research, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

Twenty-year field evidence reveals crop-specific impacts of conservation tillage on yield in a rice-wheat system - Yalin Yu; Menghan Dong; Yuanchang Xia; Bin Sun; Yanling Li; Ahmad Latif Virk; Haishui Yang; Feng-Min Li; Shiping Liu; Zheng-Rong Kan (Field Crops Research, 2026)

Metabolic engineering of Pichia pastoris for high-efficiency production of branched-chain amino acids -enriched single-cell protein - Cancan Dong; Kai Hong; Fan Wu; Yanfeng Wang; Youyan Rong; Xin Wu; Jian Zhang; Le Gao (Bioresource Technology, 2026)

Aquaporin-1 stabilizes β-catenin to promote NLRP3 inflammasome-mediated pyroptosis in rheumatoid arthritis - Meng-yuan Zhou; Zi-yao Gao; Jing Sun; Wen-cai Long; Juan Zhou; Wen-jing Fang; Xue-chun Wang; Sheng-dong Wu; Rong Li (Apoptosis, 2026)

Trichoderma maomingense (Sordariomycetes, Hypocreaceae), a New Species Isolated From Bamboo in Guangdong Province, China - Dai‐Yan Huang; Qiu‐Rong Huang; Zhang‐Yong Dong; Mei Luo (New Zealand Journal of Botany, 2026)
Trichoderma species are widely distributed across various habitats worldwide and play significant roles in the biological control of plant diseases, plant growth promotion, and soil improvement. In this study, a novel Trichoderma species was isolated from dead culms of Bambusa cerosissima McClure in Maoming City, Guangdong Province, China. Based on morphological characteristics and multigene phylogenetic analyses of translation elongation factor 1 α ( tef1‐α ), nuclear internal transcribed spacer of rDNA region (ITS), and RNA polymerase second largest subunit ( rpb2 ) by both maximum likelihood (ML) and bayesian inference (BI) approaches, three isolates were identified as a new species within the Koningii‐clade, named Trichoderma maomingense sp. nov. The distinctions between this new species and its closely related taxa are discussed in detail.

Physical properties as the key bridge from structure-activity relationship to AI-guided rational design of food-derived bioactive peptides: A systematic review - Huizhen Xing; Huimin Dong; Chengzhi Guo; Zhigao Wang; Rong He (Trends in Food Science & Technology, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Single and combined impacts of antibiotics on aerobic denitrification: Cell growth characteristics and functional genes expressions - Rong-Rong Chang; Chang-Ze Shi; Yun-Jie Ruan; Bao-Cheng Huang; Ren-Cun Jin; Ming Dong; Wen-Bing Li (Journal of Environmental Sciences, 2026)

Rice bran protein-based self-propelled nanomotors for targeted delivery of dihydroquercetin: A food-grade nano-system for anti-atherosclerosis - Huizhen Xing; Huimin Dong; Chengzhi Guo; Yucheng Zou; Zhigao Wang; Xiaohu Luo; Rong He (Food Research International, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Predicting the kinetics of Cu release and transport in contaminated soils in the field - Liang Dong; Rong Li; Wenxia Wang; Zhifang Xiao; Zezhen Ren; Qianting Ye; Zhenqing Shi (Applied Geochemistry, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Microbial processing of organic matter in cold seep sediments revealed by amino compound distributions and degradation indices - Yang Wu; Lina Lyu; Meiqing Lin; Shengtao Ma; Cheng Yang; Rong Wu; Kaiqin Huang; Xi Xiao; Yifei Dong; Binbin Guo; Danyi Su; Jing Zhao; et al. (Marine Pollution Bulletin, 2026)

Fatal infection of a novel canine/human reassortant H3N2 influenza A virus in the zoo-housed golden monkeys - Xia Wen; Rong Chen; Yingjun Lv; Jinzhu Geng; Jingjing Guo; Yaru Sun; Aohan Yang; Yuhao Dong; Meirong Li; Changlin Deng; Guodong Wang; Yongjie Liu (Veterinary Microbiology, 2026)

Corrigendum to “Spectral properties and remote sensing of snow algal blooms in the Antarctic Peninsula” [Remote Sensing of Environment, volume 328 (2025), 114839]. - Barjeece Bashir; Dong Liang; Rong Cai; Faisal Mumtaz; Lingyi Kong; Yahui Zou (Remote Sensing of Environment, 2026)

Preharvest melatonin application enhances soft rot resistance in kiwifruit through the jasmonic acid signaling pathway - Junsen Peng; Shufeng Du; Rong Fan; Youhua Long; Guofang Xie; Xiaochun Ding; Xiaoqing Dong (Postharvest Biology and Technology, 2026)

The candidate effector Bd_A04480 contributes to Botryosphaeria dothidea-induced postharvest soft rot in kiwifruit by increasing virulence and suppressing plant immunity - Hong Tan; Jinhuang Song; Juanrong Qin; Shufeng Du; Rui Yang; Xiaoqing Dong; Zhibo Zhao; Youhua Long; Rong Fan (Postharvest Biology and Technology, 2026)

Beyond electrostatic interaction: Ball milling-induced dominance of pore filling and π-π stacking for methylene blue adsorption on tobacco stem derived activated carbon - Dong-Can Lv; Meng-Ru Chen; Mei-Rong Song; Guang-Ce Jiang; Zhi-Min Wang (Journal of Water Process Engineering, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

From origin tracing, processing, to quality regulation: Molecular mechanism advances in medicinal foods research by integrating multi-omics tools - Jian-Hang Cai; Guan-Dong Fang; Yan Zhang; Jie Song; Jia-Yi Weng; Xue-Mei Ge; Issoufou Amadou; Xiang-Rong Cheng (Food Bioscience, 2026)

Revealing the role of spin state in catalysis: Medium spin Fe3+ catalyst for lithium‑sulfur batteries - Xin Dong; Rong Yang; Xifei Li; Peiying Li; Yurou Wang; Xuchen Li; Hongyu Shang; Jiaze Li; Chaojiang Fan; Yinglin Yan; Yunhua Xu (Chemical Engineering Journal, 2026)

Grass roots on gully bed inhibit plunge pool development but have a limited influence on headcut retreat: a case study based on an in-situ experiment in dry-hot valley of southwest China - Yanping Liu; Yifan Dong; Jie Feng; Ronghua Zhong; Li Rong (CATENA, 2026)

Response of cloud microphysics to aircraft-based glaciogenic seeding of supercooled clouds in North China - Xiaobo Dong; Baojun Chen; Jing Yang; Rong Mai (Atmospheric Research, 2026)

The effect of rare earth elements (REEs) on plant growth promotion: a review on mechanisms and the role of REE-dependent methylotrophs - Chang-Dong Liu; Jia-Chen Zhao; Wen-Shen Liu; Antony van der Ent; Rong-Liang Qiu; Jean Louis Morel; Ye-Tao Tang (Plant and Soil, 2026)

Direct and sensitive SERS detection of aflatoxin B1 based on aggregated silver nanocages - Rongjing Hu; Jiadan Zhang; Jingwen Zhang; Jiefeng Rong; Fengfu Fu; Zhenyu Lin; Yongqiang Dong (Analytica Chimica Acta, 2026)

Cu–N4 active site sensing platform for point-of-care colorimetric detection of environmental organophosphorus pesticide - Rong Huang; Zhong Dong; Wanyi Zhang; Zhenggang Xue; Dongmei Deng; Wei Wang; Yuanyuan Li; Haibo He; Liqiang Luo (Analytica Chimica Acta, 2026)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Freeze–thaw–induced regulation of petroleum hydrocarbon adsorption in cold-region soils: Role of organic matter dynamics - Rong Zhong; Hang Lyu; Xiaosi Su; Xinyue Yan; Yun Teng; Weihong Dong; Yuyu Wan; Tiejun Song; Xiaofang Shen (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

One new aryltetralin lignan and other components from Blachia pentzii - Yan-Yan Zhang; Feng-Cheng Zhang; Yue Zhang; Hong-Yan Yu; Hai-Rong Xu; Xiao-Yun Dong; Chang-Shui Yang (Phytochemistry Letters, 2025)

Mixed grazing of lambs and ewes improves lamb growth performance by reducing foraging time and activity-related energy expenditure - Pengzhen Li; Zhenhao Zhang; Yao Dong; Chengtong Guo; Yuping Rong (Journal of Environmental Management, 2025)

Engineering sulfoxide synthases for efficient microbial production of ergothioneine: Mechanisms, strategies, and perspectives - Xiaodi Wei; Lijuan Liu; Sheng Dong; Pingle Wu; Xiao Zhang; Min Yang; Rong Zheng; Haibo Zhang (Food Chemistry, 2025)

Construction of antibacterial-enhanced 2D ZnO@ZIF-8 nanocomposites based on synergistic antimicrobial mechanisms and application in maize long-term storage - Song-Yue Xu; Chao-Shuai Mei; Ke-Yu Zhou; Feng Xiao; Min Zhang; Qiong Wu; Yu-Rong Zhang; Dong-Dong Zhang (Food Chemistry, 2025)

Ginkgolic acids-enriched nanoemulsions: A green strategy for broad-spectrum antimicrobial delivery - Qihui Dong; Rong Wu; Jun Cao; Fuliang Cao; Pengfei Yu; Erzheng Su (Food Chemistry, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Imidazole-modified separator for uniform polysulfide anchoring and accelerated redox in Li S batteries - Xiangwei Zhao; Qin Dong; Wei Hong; Rong Li; Xinglong Gou; Ruiyi Gan; Tao Wang; Cunpu Li (Chemical Engineering Journal, 2025)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Investigation of the Shallow Structure of the Hami Basin Northern Margin Fault Using Comprehensive Geophysical Methods - Guang-hong Ju; Xiao-dong He; Rong-ying Zheng; Yan-ling Liu; Jun-qi Duan; Jun Shen; Zhi-tao Gao (Applied Geophysics, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Trichoderma azadirachtae Ta3302: A novel biocontrol agent for banana Fusarium wilt and a promoter of plant growth - Mei Luo; Qiu-Rong Huang; Meng-Xuan Jia; Jin-Ying Zeng; En-Ru Dong; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2025)

AIEgen-based porous organic polymer-Ag nanoparticles hybrids with coreaction accelerator amplification and covalent rigidification-enhanced electrochemiluminescence for aflatoxin M1 detection - Jun-Qi Song; Qiu-Yi Peng; Mei-Ling Lu; Shu-Zhen Gao; Wen-Bin Liang; Shaoguang Sun; Ruo Yuan; Dong-Rong Xiao (Food Chemistry, 2025)

Efficient strategy for fructose conversion to 2,5-furandicarboxylic acid, 2,5-dicarbonylfuran or 5-formyl-2-furancarboxylic acid over dual single-atomic Fe/Co catalyst - Maolin Li; Quanxi Lu; Zhichao Dong; Sijie Liu; Rong Tan (Chemical Engineering Journal, 2025)

Novel pyrene-based metal-organic framework nanosheets' metal ions directly serve as coreaction accelerators to boost their electrochemiluminescence performance for fabricating supersensitive biosensor - Qiu-Yi Peng; Qiu-Yue Li; Yang Yang; Jun-Qi Song; Bing-Ling Yu; Wen-Bin Liang; Yan Li; Ruo Yuan; Dong-Rong Xiao (Chemical Engineering Journal, 2025)

Direct oxidation of trace methane to formaldehyde under ambient conditions by piezo-photocatalytic synergy - Qiyu Zhang; Li Rong; Yue Jiang; Zhiping Zhu; Xiaochang Lin; Yongzhen Ding; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2025)

Synergistic Cr(VI)/Oxytetracycline co-removal via acid-stable non-radical pathways enabled by plasmonic Z-scheme W18O49/Bi4NbO8Cl heterojunction - Chu-Jia Jin; Huai-Yuan Niu; Lei Ma; Ya-Ya Yang; Long Sui; Zheng-Tao Dong; Yan-Rong Peng; Ming Yan; Cheng-Gang Niu (Chemical Engineering Journal, 2025)

O304 is a mitochondrial uncoupler which extends C. elegans lifespan and induces vasorelaxation of rat mesenteric arteries - Wen-Feng Li; Yi Zeng; Yi-Dan Zhang; Rong Zhang; Jing Lang; Wen-Jie Bu; Meng-Ke Zhao; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Bio-organic fertilizer amendment helps suppress tomato bacterial wilt disease by improving aggregation and enhancing the pathogen inhibition capacity within micro-aggregates - Menghui Dong; Eiko E. Kuramae; Mengli Zhao; Yi Min; Shanshan Liu; Xu Xu; Qirong Shen; Rong Li; George A. Kowalchuk (Biology and Fertility of Soils, 2025)

Spectral properties and remote sensing of snow algal blooms in the Antarctic Peninsula - Barjeece Bashir; Dong Liang; Rong Cai; Faisal Mumtaz; Lingyi Kong; Yahui Zou (Remote Sensing of Environment, 2025)

Daily temperature fluctuations intensify the toxicokinetics and toxicodynamics of phenanthrene in Enchytraeus albidus (Oligochaeta), increasing overall toxicity risk - Naichuan Xiao; Ming Gao; Dong Zhu; Zifang Wang; Rong Huang; Lelin You; Tingting Zhang; Wencai Dai (Journal of Hazardous Materials, 2025)

R-P phase high-entropy perovskite La0.5Sr1.5Mn0.2Fe0.2Ni0.2Cu0.2Co0.2O4 achieves complete PMS utilization via multi-pathway activation for efficient water purification - Lei Ma; Huai-Yuan Niu; Chu-Jia Jin; Long Sui; Zheng-Tao Dong; Yan-Rong Peng; Ming Yan; Cheng-Gang Niu (Chemical Engineering Journal, 2025)

From ultrafiltration to nanofiltration: structural engineering of polyetherketone membranes via additive-assisted thermal crosslinking for superior organic solvent resistance - Xiangmin Xu; Yuefei Rong; Mengjie Hou; Meudjeu Tognia; Xinyu Dong; Lin Li; Tonghua Wang (Chemical Engineering Journal, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Room temperature natural light promoted DMSO/O2-catalyzed N-acylation reaction of imidazoles/triazoles with cyclopropenones - Guo-Dong Shen; Zhi-Rong Zhao; Kun Bi; Yi Man; Jun-Tong Liu; Xian-Qiang Huang; Xin Lv (Molecular Diversity, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Antimicrobial-enhanced nanoparticles based on self-assembly effects: principles, properties and applications in food - Song-Yue Xu; Jin Zhang; Ke-Yu Zhou; Min Zhang; Qiong Wu; Yu-Rong Zhang; Dong-Dong Zhang (Trends in Food Science & Technology, 2025)

Enhancing urban biosecurity and sustainability through a microclimatic bioaerosol risk management framework - Zhijian Dong; Zhijian Liu; Yongjun Jin; Haiyang Liu; Chenxing Hu; Chenglin Ye; Yaohua Yuan; Rui Rong (Sustainable Cities and Society, 2025)

Analysis of energy consumption and carbon emissions of electric arc furnace steelmaking using hydrogen-based direct reduced iron - Botao Xue; Guangsheng Wei; Biao Dong; Conejo Alberto N; Hongbin Wang; Rong Zhu (Process Safety and Environmental Protection, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Phthalocyanine-based nanosensitizers for enhanced sonodynamic therapy activity of hypoxic tumor with dual apoptosis/ferroptosis pathways - Xue-Yan Li; Jin Liu; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Network-based insights into the temperature-driven mechanisms of bacterial self-assembly in the solid-state fermented vinegar seed Pei - Mingchao Jiang; Yiyang Zou; Yuhang Wang; Yunsong Yang; Dong Han; Wenting Li; Yuanyuan Zhu; Yuqin Wang; Zhen Yu; Ke Wang; Chunchi Rong; Peng Liu; et al. (Food Bioscience, 2025)

Inhalable dexamethasone-loaded zwitterionic nanomicelles enabling effective penetration of the mucus barrier for acute lung injury treatment - Rong Chen; Xiangrong Dai; Rongjiao Sun; Yi Liao; Jiajia Dong; Ying Tan; Xuru Jin (Chemical Engineering Journal, 2025)

The application of hyper dose drug derived cell vehicles theory in gouty arthritis: Phoenix nirvana — A non-living mesenchymal stem cell drug delivery system - Chengran Wang; Xinao Rong; Tianqi Dong; Jinqi Zhu; Fangruyue Wang; Pu Shao; Jinlan Jiang (Chemical Engineering Journal, 2025)

Application of biochar in saline soils enhances soil resilience and reduces greenhouse gas emissions in arid irrigation areas - Shixiong Ren; Jiawang Zhong; Kai Wang; Rong Liu; Hao Feng; Qin’ge Dong; Yuchen Yang (Soil and Tillage Research, 2025)

A hybrid biomanipulation strategy to regulate seasonal dynamics of phytoplankton in a subtropical mesocosm experiment - Feng Wang; Wenyi Dong; Hongjie Wang; Xiaohui Sun; Helong Song; Zijun Dong; Zhiqiang Zuo; Botao Ni; Yanbing Ni; Chen Lin; Yiping Rong; Xi Lin (Science of The Total Environment, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Regulatory measures for mitigating physical and mental health impacts in aerospace environment: A systematic review - Rong Liang; Jing Gao; Xiaohui Liu; Xinyao Li; Haonan Chang; Rongdian Yang; Jiajia Yang; Dong Ming (Life Sciences in Space Research, 2025)

Low-valent Cu doping optimizes Ruddlesden-Popper perovskite for accelerated levofloxacin removal: Enhanced Ni-dominated dual radical/nonradical pathways - Lei Ma; Chu-Jia Jin; Huai-Yuan Niu; Zheng-Tao Dong; Long Sui; Qian Wu; Yan-Rong Peng; Jia-jia Wang; Cheng-Gang Niu (Journal of Hazardous Materials, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

Dynamic performance tests and multi-parametric refinement models of high-energy dissipation viscoelastic materials for seismic performance enhancement of engineering structures - Yao-Rong Dong; Zhao-Dong Xu; Lihua Zhu; Bao-Shun Wang; Yang Yang; Yu Cheng (Engineering Structures, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Corrigendum to “In-situ grown cauliflower-like CuSn zinc anodes with permselective PEDOT: PSS coating for synergistic construction of long-cycle dendrite-free zinc ion batteries” [Chem. Eng. J. 508 (2025) 161005] - Yanjing Rong; Junwen Duan; Quan Kuang; Zhixiong Xu; Yunbo Li; Jianguo Li; Qinghua Fan; Youzhong Dong; Yanming Zhao; Yunhua Cheng (Chemical Engineering Journal, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Low Nitrogen with Split Application Strategy Enhances Antioxidative Defense, Photosynthesis, and Enzymatic Activities to Waxy Maize Under Heat Stress - Song Xu-dong; Ahmad Irshad; Zhang Hui-min; Zhang Zhen-liang; Zhou Guang-fei; Chen Guo-qing; Mao Yu-xiang; Lu Hu-hua; Hao De-rong (Journal of Plant Growth Regulation, 2025)

Understanding the delayed onset of the South China Sea summer monsoon in CMIP6 models - Jie Yang; Shaobo Qiao; Xueying Wang; Rong Deng; Shankai Tang; Xian Zhu; Wenjie Dong (Climate Dynamics, 2025)

Antibiotics shape the core microbial community distribution between floc and biofilm in an endogenous partial denitrification system: Insight from metabolic pathway - Kai-Yue Dong; Chao-Xi Yang; Jin-Luo Pang; Rong-Rong Chang; Ke-Yu Chen; Wei Yao; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2025)

Analysis of CO2 emission and energy consumption in CCUS for steel-chemical joint production - Huapeng Yang; Chao Feng; Tao Lin; Rong Zhu; Kai Dong; Guangsheng Wei; Mingwei Tu; Fuhai Liu; Ziheng Zhao; Xin Ren; Chunyang Wang (Journal of Environmental Management, 2025)

Optimization of moisture content and duration in low-speed rotational thermostatic tempering for enhanced physicochemical properties of indica rice flour - Rong Dong; Wenkang Luo; Xiwu Jia; Wenjing Huang; Jian Xia; Zhan Wang (Journal of Cereal Science, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Ant colony-inspired cooperative control of multi- magnetorheological dampers system for coupled vibration mitigation of spatial irregular structures - Yang Yang; Zhao-Dong Xu; Xing-Huai Huang; Yao-Rong Dong; Jun Dai; Yuan-Jin Li (Engineering Structures, 2025)

Enhanced ecological risks of pollutant-adsorbed engineered environmental particles to soil microorganisms - Quan Chen; Yue Zhang; Wan-Rong Zhang; Yu Huang; Min Wu; Hong-Zhe Li; Yi-Yue Zhang; Yi-Fei Wang; Dong Zhu; Philippe Frangois-Xavier Corvini; Bo Pan (Chemical Engineering Journal, 2025)

Analysis of anomalous cloud-to-ground lightning in a Wuhan tornadic supercell on 14 May 2021 - Rong Yu; Muyun Du; Dong Zheng; Jue Wang (Atmospheric Research, 2025)

Anthropogenic Influence on the Compound Hot and Dry Event in Summer 2022 in the Tibetan Plateau Based on Statistical Downscaling CMIP6 Models - Kening Xue; Wei Li; Siyan Dong; Rong Yu; Leibin Wang (International Journal of Climatology, 2025)
In the summer of 2022, the Tibetan Plateau experienced a record‐breaking compound hot and dry event (CHDE). This study quantifies the contribution of anthropogenic influence to this compound event using a set of high‐resolution statistical downscaling results from six CMIP6 models. The Copula function was used to calculate the joint probability of the compound event. The results show that in the summer of 2022, hot conditions in the Tibetan Plateau broke records since 1961, with a return period of 408 years. The dry conditions were also uncommon, with a return period of 47 years. The hot and dry compound event is particularly rare, with a return period of more than 20,000 years. Based on the results from statistical downscaling models, it was found that anthropogenic influence has increased the risks of dry and hot conditions similar to those in the Tibetan Plateau in 2022 by factors of 3.3 [1.5, 5.2] and 14 [8.6, 21.2], respectively. Additionally, the risk of compound events has been increased by a factor of 46.7 [26.7, 77.6]. In the future, with the intensification of warm‐wet situations on the Tibetan Plateau, the hot conditions similar to 2022 are expected to increase remarkably, with the risk of occurrence rising by factors of 56 [34, 108] and 75 [44, 162] during the periods 2021–2040 and 2051–2070, respectively. Conversely, dry conditions are projected to decrease, with reductions of 0.21 [0.075, 0.46] and 0.51 [0.3, 1.2] times in the two future periods. However, the risk of compound events is expected to increase, with increases of 3.3 [1.5, 5.2] times and 11 [6, 25] times during the two periods. This study is the first to use downscaled simulation to conduct event attribution analysis for the Tibetan Plateau, which can deepen the understanding of the influence of human activities on compound events.

Multi-stage risk assessment and evacuation strategy for promoting urban resilience in the face of bioaerosol leakage under various meteorological information - Zhijian Liu; Yuchen He; Chenxing Hu; Rui Rong; Zhijian Dong; Chenglin Ye; Li Chen (Urban Climate, 2025)

MilTilV: a vertically resolved microbial explicit soil organic carbon turnover model integrated the effect of tillage operation - Kaihao YE; Liang DONG; Yijin LV; Wenxia WANG; Zhifang XIAO; Junran LI; Zhenqing SHI; Rong LI (Pedosphere, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Ambient air pollution and the risk of cancer: Evidence from global cohort studies and epigenetic-related causal inference - Dong Peng; Xiao-Yu Liu; Yuan-Hui Sheng; Si-Qi Li; Dan Zhang; Bo Chen; Pei Yu; Zhao-Yuan Li; Shuai Li; Rong-Bin Xu (Journal of Hazardous Materials, 2025)

Assessment of fate of respiratory droplets and effectiveness of different air cleaners during outpatient consultation - Haiyang Liu; Zhijian Liu; Guangpeng Yao; Zhijian Dong; Chuan Jiang; Jingwei Liu; Rui Rong; Junzhou He; Chenxing Hu; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

Hydrolytic degradation of nerve agent simulants accelerated by host-guest gold nanozymes - Qingqing Sun; Mengyuan Wang; Qingqing Wen; Haili Dong; Yanchao Lyu; Jie Han; Rong Guo (Chemical Engineering Journal, 2025)

Ultra-stable all-solid-state lithium metal batteries facilitated by in-situ LiF-rich single-ion conductor composite polymer electrolytes - Jiaze Li; Rong Yang; Aoyi Jiang; Qianwei Zhang; Xin Dong; Hongyu Shang; Yinglin Yan; Yunhua Xu; Jou-Hyeon Ahn (Chemical Engineering Journal, 2025)

A high-performance flexible force sensitive conductive composite with programmed digital crack by femtosecond laser etching - Rong Zhang; Xuejiao Shen; Deyuan Lou; Chaoshuai Dong; Qingyan Liu; Qian Liu; Qingting Liu; Xudong Fu; Shengfei Hu (Chemical Engineering Journal, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Transcriptome and Metabolome Combine to Analyze the Mechanism of Leaf Coloration Formation in Aeonium arboreum ‘Pink Sybil’ - Suhua Li; Rong Zhao; Haozhang Han; Lihua Zhang; Fang Wang; Nan Zhang; Rong Dong (Plant Molecular Biology Reporter, 2025)

Nrf2 Ameliorates Sevoflurane-Induced Cognitive Deficits in Aged Mice by Inhibiting Neuroinflammation in the Hippocampus - Junhua Li; Jinfeng Li; Yafang Liu; Chuwen Hu; Hui Xu; Dong Cao; Rong Zhang; Kun Zhang (Molecular Neurobiology, 2025)

Corrigendum to ‘Carbon black nanoparticles induce pulmonary fibrosis through NLRP3 inflammasome pathway modulated by miR-96 targeted FOXO3a’ [Chemosphere (2020) 125075] - Lixiao Zhou; Peiyuan Li; Mengyue Zhang; Bin Han; Chen Chu; Xuan Su; Binghua Li; Hui Kang; Jie Ning; Boyuan Zhang; Shitao Ma; Dong Su; et al. (Chemosphere, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Identification of key risk ships in risk-based ship complex network - Qian Qiao; Rong Zhen; Han Dong; Shuwu Wang; Qionglin Fang (Ocean Engineering, 2025)

BFRP bars reinforced geopolymer-based coral aggregate concrete beams with sustainable and high seawater erosion resistance: Flexural durability, economic, and ecological analysis - Bai Zhang; Hong Zhu; Zhiyuan Yang; Yao-Rong Dong (Engineering Structures, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Thermosensitive poly (NVCL-co-GelMA) nanogels as a delivery platform for rectal administration of 5-ASA in ulcerative colitis - Rongjiao Sun; Limei Zhu; Xianzhu You; Rong Chen; Jiante Li; Rongrong Pan; Yueqi Jin; Hua Zhou; Ying Tan; Jiajia Dong; Wanle Hu (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Melittin: A promising therapeutic agent for rheumatoid arthritis treatment - Rong Huang; Xiying He; Qingxin Meng; Guangyu Yan; Kun Dong; Yakai Tian (Toxicon, 2025)

Steering CO2 electroreduction to hydrocarbons over 2D thiol-based conductive metal-organic framework - Qiu-Jin Wu; Duan-Hui Si; Yu-Liang Dong; Qian Chen; Li-Li Han; Rong Cao; Yuan-Biao Huang (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

Interdecadal variation in the relationship between ENSO and summer precipitation in the middle and lower reaches of the Yangtze River - Rong Zhi; Taichen Feng; Wenjie Dong; Yuheng Zhao; Jieli Hong (Climate Dynamics, 2025)

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Hydroxysafflower yellow A alleviates the inflammatory response in astrocytes following cerebral ischemia by inhibiting the LCN2/STAT3 feedback loop - Lijuan Song; Yige Wu; Lijun Yin; Yanzhe Duan; Jianlin Hua; Mengwei Rong; Kexin Liu; Junjun Yin; Dong Ma; Ce Zhang; Baoguo Xiao; Cungen Ma (Metabolic Brain Disease, 2025)

Large-scale crop dataset and deep learning-based multi-modal fusion framework for more accurate G × E genomic prediction - Qixiang Zou; Shuaishuai Tai; Qianguang Yuan; Yating Nie; Heping Gou; Longfei Wang; Chuanxiu Li; Yi Jing; Fangchun Dong; Zhen Yue; Yi Rong; Xiaodong Fang; et al. (Computers and Electronics in Agriculture, 2025)

Extraction of short-chain fatty acid ethyl Ester in Baijiu using covalent organic framework–based magnetic nanoparticles: Theoretical screening and experimental validation - Xiaolong Shang; Ying Han; Xudong Lian; Siting Ye; Ling Ao; Baoguo Sun; Rong Liu; Pan Zhen; Yongqing Zhang; Yintao Jia; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Toxic aldehydes in fried foods: Formation, analysis, and reduction strategies - Xing-yang Guo; Liang-yu Cheng; Chao Chang; Xiao-ming Jiang; Pan Gao; Wu Zhong; Chuan-rong Hu; Dong-ping He; Jiao-jiao Yin (Food Control, 2025)

Thermal comfort and urban microclimate response: A new thermal environment assessment model for waterfront spaces in historic ancient towns - Yan Wang; Xinrui Liu; Rong Xie; Jiajing Wang; Qiwei Dong; Wanxiang Yao; Dahu Lin (Energy and Buildings, 2025)

In-situ grown cauliflower-like CuSn zinc anodes with permselective PEDOT:PSS coating for synergistic construction of long-cycle dendrite-free zinc ion batteries - Yanjing Rong; Junwen Duan; Quan Kuang; Zhixiong Xu; Yunbo Li; Jianguo Li; Qinghua Fan; Youzhong Dong; Yanming Zhao (Chemical Engineering Journal, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Effects of crop rotation on plant- and microbial-derived carbon within particulate and mineral fractions in paddy soils - Yalin Yu; Ningxuan Zhu; Ying Ren; Menghan Dong; Guofeng Sun; Ahmad Latif Virk; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Agriculture, Ecosystems & Environment, 2025)

Research on Optimization Method for Irregular Seismic Acquisition in Curved Wave Domain Based on Simulated Annealing - Hu Zhao; Meng-yang Chen; Yu-dong Ni; Rong-rong Zhao; Fu-hao Jiang; Wei Chen; Jing-yun Dai (Applied Geophysics, 2025)

Soil bacterial community composition but not alpha diversity altered along a gradient of Spartina alterniflora invasion on the coast of Yellow Sea, China - Li Yang; Yue Peng; Shuang Wang; Chenxuan Rong; Huice Dong; Hongshan Li; Baoming Ge (Frontiers in Marine Science, 2025)
Introduction Spartina alterniflora invasion may alter the characteristics and functions of the coastal wetland ecosystems. Previous studies have shown that invasion changes the biogeochemical processes and microbial diversity in marsh ecosystems; however, knowledge of the changes in bacterial communities and their function at different soil depths during invasion remains limited. Methods In the present study, we investigated S. alterniflora invasion on the dynamic changes of soil bacterial communities using Illumina MiSeq sequencing analyses of 16S rRNA at different soil depths (i.e., 0–10, 10–20, and 20–40 cm) during the invasive process (i.e., 1, 4, 7, and 12 years), as well as the potential correlations between soil physicochemical characteristics and enzyme activities. Results The invasion of S. alterniflora did not significantly affect soil bacterial alpha diversity or the functional profiles at the first and second levels of the Kyoto Encyclopedia of Genes and Genomes (KEGG). Furthermore, no significant changes were observed across different soil depths. However, the relative abundances of Chloroplast and Alphaproteobacteria increased from 3.03% and 5.05% in bare mudflat to 13.61% and 8.95% in the 12-year-old S. alterniflora invaded soil, respectively, whereas those of Deltaproteobacteria, Acidimicrobiia, and Bacilli decreased after S. alterniflora invasion for approximately 12 years. The relative abundances of soil bacteria varied with soil depth. Total phosphorus, carbon-to-nitrogen ratio, total carbon, and catalase activity were the key factors affecting soil bacterial community composition. Discussion The soil physicochemical characteristics changes caused by invasion may temporarily enhance soil fertility, they can lead to long-term wetland degradation through changed biological community and altered nutrient dynamics. This study provides a comprehensive understanding of the dynamic changes in bacterial communities, soil physicochemical characteristics, and enzyme activities during S. alterniflora invasion on coastal wetlands.

Effects of microclimatic conditions and urban building configurations on aerodynamic characteristics and health risks of bioaerosols: Insights from idealized urban models - Zhijian Dong; Zhijian Liu; Chenxing Hu; Chenglin Ye; Yongjun Jin; Haiyang Liu; Rui Rong; Yuchen He; Li Chen; Chuanchen Li; Yaolong Shi; Yufeng Su (Sustainable Cities and Society, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Revisiting bipolar membrane electrodialysis for the production of monoprotic organic acids with different p K a and Mw - Rong Zhou; Zhiguo Dong; Xixi Ma; Lili Xue; Jinxin Liu; Jinfeng He; Weiwei Li; Li Sun; Chuanrun Li; Haiyang Yan (Chemical Engineering Journal, 2025)

Wind tunnel experiments on bioaerosol dispersion and exposure risk assessment in wastewater treatment plants under natural ventilation - Zhijian Liu; Chuanchen Li; Chenxing Hu; Rui Rong; Yaolong Shi; Zhijian Dong; Chenglin Ye; Chuang Zhang (Building and Environment, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Upper ocean salinity and temperature changes and their contributions to the stratification in the tropical Pacific under global warming - Hai Zhi; Rong-Hua Zhang; Meng Dong; Minmin Wu (Climate Dynamics, 2025)

Thermodynamic processes prolong triple La Niña events in a hybrid coupled ocean-atmosphere model - Xiang Dong; Rong-Hua Zhang; Junya Hu; Chuan Gao; Maonan Chen (Climate Dynamics, 2025)

Impacts of lake basin topography predicted by long short-term memory on difference of lake area and water resource evolution - Ruirui Jiang; Rong Ma; Lefan Zhao; Wanggang Dong; Ruiqing Zhou (Journal of Cleaner Production, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Inhibition of fungal mycelial growth and mycotoxin production using ZnO@mSiO2 nanocomposite during maize storage - Song-Yue Xu; Zi-Yi Wang; Qiong Wu; Feng-Wei Hu; Jin-Feng Zhao; Yu-Rong Zhang; Dong-Dong Zhang (Food Bioscience, 2025)

Structural evolution of CO2 emissions outsourcing within the global ICT multinational investment network - Xiaoping Zhang; Tao Zhao; Hao Feng; Yujie Wei; Rong Yuan; Liang Dong (Environmental Impact Assessment Review, 2025)

Fast detection of NO2 by In2O3@ZnO nanofibers synthesized by coaxial electrospinning: Real-time monitoring application of smart mask - Xingyu Kang; Haibo Yu; Xiao Ma; Eryang Shang; Hong Chen; Huizhang Zhao; Jiawei Zhang; Rong Tan; Dong Wang; Hairui Fang (Chemical Engineering Journal, 2025)

Lignocellulosic biowaste hydrothermal humification: Is there a method for predicting humic acid? - Yuchao Shao; Jianchao Wang; Zhiqiang Dong; Yujie Wang; Wenjing He; Weizhong Huo; Rong Ye; Yanqing Liu; Kexue Liu; Jialin Xue; Wenjing Lu; Tianxue Yang (Chemical Engineering Journal, 2025)

Weavable composite filament for sustained electricity generation from multiple sources - Rong Liu; Haoyu Li; Zhenzhou Fu; Hailou Wang; Jiamu Dai; Kai Dong; Ick Soo Kim; Wei Zhang (Chemical Engineering Journal, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

A novel collaborative collision avoidance decision method for multi-ship encounters in complex waterways - Han Dong; Rong Zhen; Qiyong Gu; Zhong Lin; Jiuhu Chen; Kai Yan; Bing Chen (Ocean Engineering, 2024)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Electrodialysis with ultrafiltration membrane for efficient isolation of oxymatrine from simulated eluent of traditional Chinese medicine - Zhiguo Dong; Rong Zhou; Zengqiang Wei; Yiwei Dong; Li Sun; Xixi Ma; Wenlong Liu; Qiuhua Li; Jinfeng He; Chuanrun Li; Haiyang Yan (Desalination, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Enhanced comprehensive energy storage properties of lead-free KNN based ceramics through composition optimization strategy - Tingting Gao; Mingyue Mo; Ning Chen; Qifan Chen; Rong Lang; Dong Wang; Zhi Tan; Jie Xing; Jianguo Zhu (Chemical Engineering Journal, 2024)

Polymerizable deep eutectic solvent enables flexible gel formation for motion sensor and anti-UV film - Shanlei Chang; Kai Rong; Yuchen Wang; Zhixuan Yu; Junfeng Zhai; Hongwei Tian; Youxing Fang; Shaojun Dong (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Experimental studies and pore-scale modeling of hydrate dissociation kinetics at different depressurization rates in a cubic hydrate simulator - Chang-Wen Xiao; Xiao-Sen Li; Hong-Feng Lu; Gang Li; Chen-Lu Xu; Rong-Rong Qi; Dong-Hui Xing; Xian Li; Yi-Fan Weng; Lu Yu (Chemical Engineering Journal, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

The concentration of dissolved organic matter impacts the neurobehavior in zebrafish larvae exposed to cyclophosphamide - Tianming Liu; Dongshen Shang; Weiqi Tian; Yindong Li; Rong Xie; Jianxing Zhao; Heru Dong (Environmental Science and Pollution Research, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Interactions between fibroblasts and monocyte-derived cells in chronic lung injuries induced by real-ambient particulate matter exposure - Youjin Zeng; Rui Zhang; Yue Jiang; Daochuan Li; Liping Chen; Guanghui Dong; Rong Zhang; Yujie Niu; Wen Chen; Shen Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Provenance evolution of the Fushan Sag (Hainan Island, Southern China): Constraints from U-Pb geochronology on detrital zircons - Qiqi Song; Jie Hu; Dong Lei; Zhiwu Li; Rong Tang; Shengbiao Hu (Marine and Petroleum Geology, 2024)

Evaluation of the safety, immunogenicity and protective effect of an attenuated Pseudomonas plecoglossicida strain ΔgacS as the live vaccine for the large yellow croaker (Larimichthys crocea) - Tian-Jing Kang; Su-Ming Zhou; Xiao Xie; Rong-Rong Ma; Dong Qian; Shan Jin; Fei Yin (Fish & Shellfish Immunology, 2024)

On-demand detachable and reuseable adhesives assembled by organic-silicon nanogels with wide applicability and excellent harsh-environment resistance - Hui Rong; Pengwei Zhao; Manhua Lu; Liandong Deng; Shuangyang Li; Xiaobin Fan; Zhanpeng Ye; Jianhua Zhang; Anjie Dong (Chemical Engineering Journal, 2024)

Tuning oxygen vacancies via photoinduced defect engineering in plasma pre-treated TiO2 for efficient solar-light-driven oxidation of trace methane - Qiyu Zhang; Jiakang Duan; Zhiping Zhu; Li Rong; Xiaochang Lin; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2024)

OsHRZ1 negatively regulates rice resistant to Magnaporthe oryzae infection by targeting OsVOZ2 - Jia-ying Sun; Zeng-ran Zhou; Yu-qi Wang; Dong-yu Zhu; Dian-rong Ma (Transgenic Research, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Genetic variation in a heat shock transcription factor modulates cold tolerance in maize - Lei Gao; Lingling Pan; Yiting Shi; Rong Zeng; Minze Li; Zhuoyang Li; Xuan Zhang; Xiaoming Zhao; Xinru Gong; Wei Huang; Xiaohong Yang; Jinsheng Lai; et al. (Molecular Plant, 2024)

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

p‑Phenylenediamine antioxidants in PM2.5: New markers for traffic in positive matrix factorization source apportionment - Nan Jiang; Xuexin Hao; Zichen Wang; Minzhen Li; Dong Zhang; Rong Cao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Hazardous Materials, 2024)

Location-dependent occurrence and distribution of metal-based nanoparticles in bay environments - Siying Ying; Ziyi Liu; Yongrong Hu; Rong Peng; Xiaoshan Zhu; Shuofei Dong; Dong Yan; Yuxiong Huang (Journal of Hazardous Materials, 2024)

Biofilm growth characteristic and footprint identification in gravity-driven ceramic membrane bioreactor with electro-coagulation under extreme conditions for roofing rainwater purification - Wei Song; Rong Ma; Zhenhao Liang; Jiawan Li; Jiahao Dong; Xing Du; Zhihong Wang; Xianhui Li (Journal of Environmental Management, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

Ti2TaC2: A novel out-of-plane ordered MXene towards flexible and cytocompatible supercapacitors - Yunfeng Guan; Lixian Jiang; Rong Zhao; Xuanke Li; Hui Zhu; Qin Zhang; Zhijun Dong; Nianjun Yang; Ye Cong (Chemical Engineering Journal, 2024)

Synergistic optimization of the water state and transport pathway in hydrogels via pullulan and directional Freezing-Assisted salting out for efficient evaporation - Huanwei Shen; Xiayue Yang; Wenhao Li; Zhihua Sha; Hongmei Luo; Zixuan Li; Sihan Dong; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

External redox couple enhanced anammox sludge activity at low temperature: Insight into intracellular resource synthesis - Rong-Rong Chang; Wei Yao; Jin-Luo Pang; Kai-Yue Dong; Yao-Yao Lu; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2024)

Integrated assessment of bioaerosol dispersion patterns and infection risk in a typical urban environment: Implications for urban biosecurity management - Zhijian Dong; Zhijian Liu; Chenxing Hu; Xuqiang Shao; Haokang Yang; Yongjun Jin; Rui Rong (Sustainable Cities and Society, 2024)

The cytochrome P450 gene CYP4g1 driven by high temperature confers abamectin tolerance on Liriomyza trifolii through promoting cuticular hydrocarbons biosynthesis - Yu-Cheng Wang; Ya-Wen Chang; Hong-Fang Xie; Wei-Rong Gong; Cheng-Dong Wu; Yu-Zhou Du (Pesticide Biochemistry and Physiology, 2024)

rTMS Ameliorates time-varying depression and social behaviors in stimulated space complex environment associated with VEGF signaling - Qing Xu; Rong Liang; Jing Gao; Yueyue Fan; Jinrui Dong; Ling Wang; Chenguang Zheng; Jiajia Yang; Dong Ming (Life Sciences in Space Research, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Superior energy storage properties with prominent thermal stability in lead-free KNN-based ceramics through multi-component optimization strategy - Qifan Chen; Hao Chen; Dong Wang; Tingting Gao; Qinyu Li; Rong Lang; Zhi Tan; Jie Xing; Jianguo Zhu (Chemical Engineering Journal, 2024)

Xonotlite nanowire interfacial layer with zincophilic behavior and ion confinement effect guiding inerratic Zn deposition - Mengyu Rong; Zhanming Gao; Na Gao; Shuaiyu Chen; Yang Wang; Dongzhi Chen; Xueying Dong; Lijing Zhang; Changgong Meng; Yifu Zhang (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Intelligent DNA-based hydrogels: An outstanding programable and biocompatible material for food applications - Guo Li; Hao Huang; Liang Zou; Xiaochen Zhang; Xingyu Lin; Miral Javed; Xingcai Zhang; Yanqun Xu; Rong Ai; Zisheng Luo; Dong Li (Trends in Food Science & Technology, 2024)

In situ visualization on the mobility of mineral associated organic matter in a microfluidics-based heterogeneous soil aggregate structure - Minru Cheng; Mingang Dong; Peng Liao; Haoran Wang; Zhenqing Shi; Rong Li (Journal of Hydrology, 2024)

The influence of vegetation restoration on soil quality in abandoned farmlands in the Yuanjiang dry-hot valley - Guanghai Wang; Yifan Dong; Li Rong; Wantao Yang; Xingwu Duan (CATENA, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Modeling the long-range transmission of airborne bioaerosol releases in a high-density urban environment - Zhijian Dong; Zhijian Liu; Chenxing Hu; Yongjun Jin; Chenglin Ye; Yuchen He; Rui Rong (Urban Climate, 2024)

Corrigendum to “Development, verification, and simulation analysis of variable friction self-centering energy dissipative brace” [Soil Dynam. Earthq. Eng. 179 (2024) 108537] - Lihua Zhu; Tong Liu; Zijie Li; Yao-Rong Dong; Jinwu Luo (Soil Dynamics and Earthquake Engineering, 2024)

Recycling drinking water treatment sludge in construction and building materials: A review - Zhi-hai He; Bin Wang; Jin-yan Shi; Hui Rong; Hong-yu Tao; Ahmed Salah Jamal; Xu-dong Han (Science of The Total Environment, 2024)

Soil inorganic carbon stock and its changes across the Tibetan Plateau during the 1980s–2020s - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Hua Zheng; Yun Xie; Li Rong; Haijuan Zhao; Shengzhao Wei (Global and Planetary Change, 2024)

Tertiary treatment of municipal wastewater in an IBFR dominated by PD/A with unique niche - Yue-ning Wang; Shi-rong Dong; Hui-long OuYang; Ting Yang; Yi Wang (Chemosphere, 2024)

Development, verification, and simulation analysis of variable friction self-centering energy dissipative brace - Lihua Zhu; Tong Liu; Zijie Li; Yao-Rong Dong; Jinwu Luo (Soil Dynamics and Earthquake Engineering, 2024)

Excessive fluoride induces ovarian function impairment by regulating levels of ferroptosis in fluorosis women and ovarian granulosa cells - Nan Geng; Siyuan Dong; Pengpeng Xie; Yi Zhang; Rong Shi; Chen Chen; Zhao Xu; Qun Chen (Reproductive Toxicology, 2024)

Comparative analysis of process selection and carbon emissions assessment of innovative steelmaking routes - Botao Xue; Guangsheng Wei; Yanze Hou; Hang Hu; HongJin Zhang; Rong Zhu; Kai Dong; Chao Feng; Lingzhi Yang; Hongbin Wang (Journal of Cleaner Production, 2024)

The concentration of dissolved organic matter impacts the neurobehavior in female zebrafish exposed to cyclophosphamide - Tianming Liu; Heru Dong; Jianxing Zhao; Dongshen Shang; Yindong Li; Rong Xie (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Effect of topographic slope on the interaction between debris flows and riparian forests - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Dong-ri Song; Wan-yu Zhao; Ke Jin (Landslides, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Long-range and cross-frequency neural modulation of gamma flicker on vigilance decrement - Rong Li; Jiayuan Meng; Jia You; Xiaoyu Zhou; Minpeng Xu; Dong Ming (Cognitive Neurodynamics, 2024)

Integrated morphological, physiological and transcriptomic analyses reveal response mechanisms of rice under different cadmium exposure routes - Qin Dong; Yingjie Wu; Haidong Wang; Bing Li; Rong Huang; Huanxiu Li; Qi Tao; Qiquan Li; Xiaoyan Tang; Qiang Xu; Youlin Luo; Changquan Wang (Journal of Hazardous Materials, 2024)

Inactivation of antibiotic resistant bacteria by Fe3O4 @MoS2 activated persulfate and control of antibiotic resistance dissemination risk - Chang Rong; Haijun Chen; Zhuowen Wang; Shiyi Zhao; Deming Dong; Jiao Qu; Na Zheng; Haiyang Liu; Xiuyi Hua (Journal of Hazardous Materials, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Rigidifying AIEgens in covalent organic framework nanosheets for electrochemiluminescence enhancement: TABE-PZ-CON as a novel emitter for microRNA-21 detection - Jin-Ling Zhang; Tian-Tian Wang; Wen-Bin Liang; Ruo Yuan; Dong-Rong Xiao (Analytica Chimica Acta, 2024)

Performance enhancement of damaged RC structures with viscoelastic dampers: Damage assessment and optimal placement - Zhao-Dong Xu; Yuxuan Tao; Yun Yang; Yao-Rong Dong; Jin Duan; Shihua Li; Hao Wang; Shuai Wang (Soil Dynamics and Earthquake Engineering, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Effects of zinc oxide nanocomposites on microorganism growth and protection of physicochemical quality during maize storage - Dong-Dong Zhang; Jin-Feng Zhao; Li-Qin Tan; Qiong Wu; Hao-Xin Lv; Yu-Rong Zhang; Min Zhang (International Journal of Food Microbiology, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Integrating a heatscape index and a Patch CA model to predict land surface temperature under multiple scenarios of landscape composition and configuration - Jianxin Yang; Linxin Bao; Si Dong; Yuying Qiu; Jing Gao; Shisi Zou; Rong Tao; Xinzhu Fan; Xinyuan Yu (Sustainable Cities and Society, 2024)

The response of crop yield, carbon sequestration, and global warming potential to straw and biochar applications: A meta-analysis - Rong Liu; Yiyun Hu; Xiangsheng Zhan; Jiawang Zhong; Peng Zhao; Hao Feng; Qin'ge Dong; Kadambot H.M. Siddique (Science of The Total Environment, 2024)

Impact of environmental supervision reform on green innovation in mineral enterprises - Jingshen Zhang; Xinzhu Zhou; Rong Bai; Haoyang Dong; Tingting Tang; Zeyu Wang; Ya Yang; Feng Huang (Resources Policy, 2024)

Flexural behavior of wet panel-to-panel groove-and-tongue joints provided with lapped U-bars - Ao Dong; Zhenyu Li; Bin Rong; Changxiang Wang; Zeming Wang; Hui Xu (Engineering Structures, 2024)

Transpiration-mimicking wood-based microfluidic aluminum-air batteries: Green power sources for miniaturized applications - Wei Wang; Liu-Liu Shen; Peiran Wu; Hui Yu; Jiansong Wang; Yipu Xu; Xiangzun Dong; Xuanxuan Cui; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2024)

Two calcium-based metal organic frameworks with long afterglow as anticounterfeiting materials - Rong-Hui Shi; Zhi-Qiang Long; Fanan Wang; Ling-Zhu Gong; Xiao-Ying Lin; Gui-Lin Zhuang; Dong-Fei Lu (Chemical Engineering Journal, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Zn(II) Coordination Polymer: Luminescence Sensing for Fe3+ Ion and Used as Metal Gel Particles Against Lung Cancer - Wen Dong; Rong Xie; Nan Yang; Shengming Liu (Journal of Fluorescence, 2023)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

The improvements of sea surface temperature simulation over China Offshore Sea in present climate from CMIP5 to CMIP6 models - Rong Deng; Shaobo Qiao; Xian Zhu; Tianyun Dong; Guolin Feng; Wenjie Dong (Climate Dynamics, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Experimental infection and co-infection with Chinese strains of Ehrlichia canis and Babesia vogeli in intact and splenectomized dogs: Insights on clinical, hematologic and treatment responses - Jilei Zhang; Jiawei Wang; Patrick John Kelly; Yuanyuan Zhang; Min Li; Jing Li; Rong Zhang; Yaoyao Wang; Ke Huang; Jinfeng You; Haixiang Qiu; Xiaofeng Zheng; et al. (Veterinary Parasitology, 2023)

Microplastics in coral reef sediments underestimated? They may hide in biominerals - Chih-Feng Chen; Yun-Ru Ju; Chiu-Wen Chen; Frank Paolo Jay B. Albarico; Yee Cheng Lim; Chongtai Ke; Yu-Rong Cheng; Cheng-Di Dong (Science of The Total Environment, 2023)

Selective galena depression mechanism of tea polyphenol in chalcopyrite flotation - Haiyang He; Jianjun Fang; Zhilian Qiu; Dianwen Liu; Haiyun Xie; Peilun Shen; Rong Peng; Liguo Peng; Shuang Qin; Shiqin Dong (Minerals Engineering, 2023)

Polymeric PDI-based photocatalytic nanoarchitectures promoting the performance of thin film composite membrane for forward osmosis water purification - Pin Zhao; Yang Hu; Xiaoqiang An; Rong Ji; Hao Liu; Hui Zhao; Weilong Song; Yuming Dong; Xinhua Wang (Chemical Engineering Journal, 2023)

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

A novel semi-empirical model for crop leaf area index retrieval using SAR co- and cross-polarizations - Rong Wang; Jing M. Chen; Liming He; Jane Liu; Jiali Shang; Jiangui Liu; Taifeng Dong (Remote Sensing of Environment, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Substrate specificity of polyphenol oxidase and its selectivity towards polyphenols: Unlocking the browning mechanism of fresh lotus root (Nelumbo nucifera Gaertn.) - Jingfang Li; Ze-yuan Deng; Huanhuan Dong; Rong Tsao; Xiaoru Liu (Food Chemistry, 2023)

In situ Strontium isotope stratigraphy of fish teeth in deep-sea sediments from the western Clarion-Clipperton Fracture Zone, eastern Pacific Ocean - Tianyi Wang; Yanhui Dong; Fengyou Chu; Wen Zhang; Xiaohu Li; Rong Su; Liyan Tian (Chemical Geology, 2023)

Development and analysis of a universal label-free micro/nano component for three-channel detection of silver ions, mercury ions, and tetracycline - Luhui Wang; Mengyang Hu; Rong Liu; Sunfan Xi; Meng Cheng; Yangyinchun Bao; Na Wang; Yafei Dong (Analytica Chimica Acta, 2023)

Exploration for cobalt/nitrogen-doped catalyst to creatinine degradation via peroxymonosulfate activation: toxicity evaluation, statistical modeling, and mechanisms study - Jiadi Liu; Yawen Dong; Yu Kang; Qian Kong; Kuaibing Wang; Feifei Mao; Yuanqing Bu; Rong Zhou; Chunyong Zhang; Hua Wu (Environmental Science and Pollution Research, 2023)

Emergence of the clinical rdar morphotype carbapenem-resistant and hypervirulent Klebsiella pneumoniae with enhanced adaption to hospital environment - Congcong Liu; Ning Dong; Xueting Huang; Zixian Huang; Chang Cai; Jiayue Lu; Hongwei Zhou; Jingren Zhang; Yu Zeng; Fan Yang; Gongxiang Chen; Zhangqi Shen; et al. (Science of The Total Environment, 2023)

Effects of organic carbon/elemental carbon and particle size on inhalation bioaccessibility of particle-bound PAHs - Chun-Xue Tang; Ying Dong; Xiao-Yu Yuan; Rong Wang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Science of The Total Environment, 2023)

Identifying influential ships in multi-ship encounter situation complex network based on improved WVoteRank approach - Yanting Tong; Rong Zhen; Han Dong; Jialun Liu (Ocean Engineering, 2023)

Multiple insights into lignin-mediated cadmium detoxification in rice (Oryza sativa) - Qin Dong; Yingjie Wu; Bing Li; Xi Chen; Lu Peng; Zulfiqar Ali Sahito; Huanxiu Li; Yulan Chen; Qi Tao; Qiang Xu; Rong Huang; Youlin Luo; et al. (Journal of Hazardous Materials, 2023)

Mechanism of arsenic distribution and migration during iron extraction by copper slag-steel slag combined reforming: A potential solution to refractory wastes - Yun Zhou; Hongyang Wang; Haichuan Wang; Kai Dong; Rong Zhu; Zhenqiang Jiang; Guangsheng Wei (Journal of Cleaner Production, 2023)

Fungal myosin-1 homologs as key molecular motors at the membrane–cytoskeleton interface - Qin-Rong Tan; Xiang-dong Li (Fungal Biology Reviews, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Influence of GI configurations and wall thermal effects on flow structure and pollutant dispersion within urban street canyons - Peng-Yi Cui; Rong Ji; Lai He; Zhen Zhang; Yang Luo; Yong Yang; Yuan-Dong Huang (Building and Environment, 2023)

Transcriptome and Metabolome Integrated Analysis Reveals the Mechanism of Cinnamomum bodinieri Root Response to Alkali Stress - Haozhang Han; Lihua Zhang; Suhua Li; Rong Zhao; Fang Wang; Rong Dong; Xiaoli Wang (Plant Molecular Biology Reporter, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Diverse early diagenetic processes of ferromanganese nodules from the eastern Pacific Ocean: evidence from mineralogy and in-situ geochemistry - Rong Su; Fengyue Sun; Xiaohu Li; Fengyou Chu; Guosheng Sun; Jie Li; Hao Wang; Zhenggang Li; Cong Zhang; Weiyan Zhang; Xiaohan Gong; Yanhui Dong (International Geology Review, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Mechanisms and adsorption capacities of ball milled biomass fly ash/biochar composites for the adsorption of methylene blue dye from aqueous solution - Huaiyan Li; Jie Kong; Haiting Zhang; Jiale Gao; Yan Fang; Jiaqi Shi; Tao Ge; Ting Fang; Yanhong Shi; Rong Zhang; Ningyuan Zhang; Xinju Dong; et al. (Journal of Water Process Engineering, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Asymmetry of Salinity Variability in the Tropical Pacific during Interdecadal Pacific Oscillation Phases - Hai Zhi; Zihui Yang; Rong-Hua Zhang; Pengfei Lin; Jifeng Qi; Yu Huang; Meng Dong (Advances in Atmospheric Sciences, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Profit versus Sustainability in Bikeshare - Huiyi Litan; Ke Rong; Youran Wu; Danxia Xie; Hanzhe Zhang; Dong Zhao (Sustainable Cities and Society, 2023)

Melt blending crystallization regulating balanced nanodomains in efficient and scalable coating processed organic solar cells - Anran Wang; Yifei Kang; Chunqing Hou; Rong Li; Yilong Song; Qingfeng Dong (Science Bulletin, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Comparison of the comb cell structure of Apis dorsata (Hymenoptera: Apidae) in two areas of China - Shangkao Deng; Rong Huang; Qingxin Meng; Shunhua Yang; Wenzheng Zhao; Yakai Tian; Xia Dong; Kun Dong; Xueyang Gong (Journal of Asia-Pacific Entomology, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Establishment of Agrobacterium-mediated transformation system to Juglans sigillata Dode ‘Qianhe-7’ - Rong Wei; Wen’e Zhang; Chunxiang Li; Zhenkun Hao; Dong Huang; Wenlong Zhang; Xuejun Pan (Transgenic Research, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Northward migration of the maximum Indian summer monsoon precipitation during the early–mid-Holocene: Evidence from sporopollen in the Andaman Sea - Zijie Yang; Chuanxiu Luo; G.M. Ariful Islam; Xuhui Dong; Xiang Su; Rong Xiang; Shuhuan Du; Yiping Yang; Shengfa Liu (Marine Micropaleontology, 2023)

A mathematical model for intracellular NO and ROS dynamics in vascular endothelial cells activated by exercise-induced wall shear stress - Xiao Zeng; Chun-Dong Xue; Yong-Jiang Li; Kai-Rong Qin (Mathematical Biosciences, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Use of Ensemble Model for Modeling the Larval Fish Habitats of Different Ecological Guilds in the Yangtze Estuary - Rong Wan; Pengbo Song; Zengguang Li; Xiangyu Long; Dong Wang; Lu Zhai (Fishes, 2023)
Estuaries provide nursery habitats for a variety of fish species of different ecological guilds and have complicated environmental conditions. In this study, we applied ensemble species distribution models (SDMs) to four abundant and different ecological guild larval fish species (Hemiculter bleekeri (freshwater guild), Pseudolaubuca sinensis (freshwater guild), Coilia mystus (brackish water guild), and Engraulis japonicus (marine guild)) to explore their suitable habitats and the fish–habitat relationships in the Yangtze Estuary. The results showed that random forest (RF) demonstrated the best performance in all single algorithms and the surface range envelop (SRE) model was scarcely accurate. The ensemble SDMs demonstrated a superior predictive ability compared with any single algorithm, with the true skill statistic (TSS) and the area under the receiver operating characteristic curve (AUC) scores being above 0.899 and 0.641, respectively. Binary presence–absence maps showed the different spatial distribution patterns of the four species. We primarily found the freshwater species (P. sinensis and H. bleekeri) present in the South Branch (west of 122° E), whereas we found the marine species (E. japonicus) anywhere except inside the South Branch (west of 121.8° E). The area for P. sinensis (1615.93 km2) was relatively larger than that for H. bleekeri (1136.87 km2). We predicted that the brackish water species (C. mystus) would most likely be present inside the North Branch (west of 122° E), Eastern Chongming, and outside the South Branch (east of 121.8° E). Salinity, as a key environmental variable, contributed to the spatial variability. A low salinity (sea surface salinity (SSS)

Four new phenolic glycosides from Dobinea delavayi - Xiu-Rong Wu; Li-Juan Lang; Yi Shen; Xiang Dong; Chao-Jiang Xiao; Bei Jiang (Natural Product Research, 2023)

Visible-light-driven photocatalytic degradation of tetracycline hydrochloride by Z-scheme Ag3PO4/1T@2H-MoS2 heterojunction: Degradation mechanism, toxicity assessment, and potential applications - Xiuyi Hua; Haijun Chen; Chang Rong; Francis Addison; Deming Dong; Jiao Qu; Dapeng Liang; Zhiyong Guo; Na Zheng; Haiyang Liu (Journal of Hazardous Materials, 2023)

Disinfection byproducts in indoor swimming pool water: Detection and human lifetime health risk assessment - Di Zhang; Shengkun Dong; Li Chen; Rong Xiao; Wenhai Chu (Journal of Environmental Sciences, 2023)

Photocatalysis-self-Fenton system over edge covalently modified g-C3N4 with high mineralization of persistent organic pollutants - Tongbin Lu; Hui Zhao; Liang Jian; Rong Ji; Chengsi Pan; Guangli Wang; Yuming Dong; Yongfa Zhu (Environmental Research, 2023)

LncRNA CFAR promotes cardiac fibrosis via the miR-449a-5p/LOXL3/mTOR axis - Mingyu Zhang; Bowen Zhang; Xiaohan Wang; Jiahang Song; Ming Tong; Zheng Dong; Jiaonan Xu; Meng Liu; Yuan Jiang; Ning Wang; Ying Wang; Zhimin Du; et al. (Science China Life Sciences, 2023)

Neoproterozoic tungsten mineralization: Geology, chronology, and genesis of the Huashandong W deposit in northwestern Jiangxi, South China - Xu-Dong Huang; Di Huang; Jian-Jun Lu; Rong-Qing Zhang; Dong-Sheng Ma; Yao-Hui Jiang; Hao-Wen Chen; Jin-Xian Liu (Mineralium Deposita, 2023)

Assessing the consistency of crop leaf area index derived from seasonal Sentinel-2 and Landsat 8 imagery over Manitoba, Canada - Taifeng Dong; Jane Liu; Jiangui Liu; Liming He; Rong Wang; Budong Qian; Heather McNairn; Jarrett Powers; Yichao Shi; Jing M Chen; Jiali Shang (Agricultural and Forest Meteorology, 2023)

A resident subsea docking system with a real-time communication buoy moored by an electro-optical-mechanical cable - Chengye Cai; Zhenwei Rong; Zheng Chen; Bo Xu; Zhanglin Wang; Sijie Hu; Yingqiang Wang; Mingru Dong; Xiangqian Quan; Yulin Si; Ying Chen; Haocai Huang (Ocean Engineering, 2023)

Aroma formation and transformation during sealed yellowing process of Pingyang yellow tea - Rong-Jian Dong; Xie-Huang Sheng; Qian-Tu Xie; Xiaolin Huang; Fujie Yan; Songbai Liu (Food Research International, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Responses of soil water-holding capacity to environmental changes in alpine ecosystems across the southern Tibetan Plateau in the past 35–40 years - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Li Rong; Jiangcheng Huang (CATENA, 2023)

Synergistic enhancement of heat transfer and thermal storage characteristics of shell and tube heat exchanger with hybrid nanoparticles for solar energy utilization - Yangyang Wu; Jiancheng Rong; Di Wang; Xuefeng Zhao; Lan Meng; Müslüm Arıcı; Changyu Liu; Ruitong Yang; Dong Li (Journal of Cleaner Production, 2023)

A novel multistage anoxic/aerobic process with sludge regeneration zone (R-MAO) for advanced nitrogen removal from domestic sewage - Lin Cao; Rong Sun; Wenyi Dong; Hongjie Wang; Zhongyi Dai; Xue Wang; Jin Xie; Hua Li (Journal of Environmental Sciences, 2023)

Novel polysaccharide from Panax notoginseng with immunoregulation and prebiotic effects - Hui-Rong Yang; Xue Li; Hao Liu; Dong-Rui Zhao; Ying-Jie Zeng (Food Bioscience, 2023)

Rapid, linear, and highly reliable structural-color switching enabled by thermal regulation of chiral nematic mesophases - Dong Li; Rong-Rong Jiang; Si-Kai Chen; Jia-Min Wu; Xiu Dong; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Environmental Factors Influence the Effects of Biochar on the Bioavailability of Cd and Pb in Soil Under Flooding Condition - Honghong Li; Zhou Li; Limei Huang; Xiaoming Mao; Yuxuan Dong; Shilong Fu; Rong Su; Yihan Chang; Chuan Zhang (Water, Air, & Soil Pollution, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Exposure to polychlorinated biphenyls (PCBs) affects the histology and antioxidant capability of the clam Cyclina sinensis - Meimei Liu; Sishao Fan; Zhichao Rong; Hao Qiu; Susu Yan; Hongwei Ni; Zhiguo Dong (Frontiers in Marine Science, 2023)
Polychlorinated biphenyls (PCBs) are environmentally persistent and highly toxic organochlorine compounds that may cause toxic effects on aquatic animals. In this study we assess the toxic effect of PCBs on a bivalve used in aquaculture, the clam Cyclina sinensis . To this end, individuals of C. sinensis were exposed for 72 h at two PCB concentrations (1 ng/L and 10 ng/L) and control (absence of PCBs). At the end of the exposure, the hemolymph, hepatopancreas, and gills samples of C. sinensis were harvested for analysis of the enzyme activity and histology. The results showed that acute PCBs exposure decreased the survival rate of C. sinensis compared to the control. Acute PCBs exposure up-regulated the enzymatic activity of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) and the content of malondialdehyde (MDA) in the hemolymph of C. sinensis , while down-regulated the non-specific enzymatic activity of alkaline phosphatase (AKP). For the hepatopancreas, 1 ng/L PCBs exposure up-regulated the enzymatic activity of SOD while down-regulated the enzymatic activity of CAT of C. sinensis . In the gill, the enzymatic activity of CAT decreased significantly and the MDA content increased of C. sinensis after 10 ng/L PCBs exposure. Moreover, histological observations showed that acute exposure to PCBs caused loss of gill filaments and lateral cilia and shortening of their length, in the studied organism. The present study will provide valuable reference data for marine shellfish aquaculture and toxicology research.

Gonad transcriptome analysis reveals the differences in gene expression related to sex-biased and reproduction of clam Cyclina sinensis - Meimei Liu; Hongwei Ni; Zichao Rong; Zi Wang; Susu Yan; Xiaoting Liao; Zhiguo Dong (Frontiers in Marine Science, 2023)
Sexual differentiation and gonad development are important biological processes for bivalve species. The clam Cyclina sinensis is an important cultured marine bivalve widely distributed along with the coastal areas of China. However, the information related to sexual determination/differentiation and gonadal development of C. sinensis almost has no reported. To study the molecular mechanisms of its sexual determination/differentiation and gonadal development, transcriptome analysis was performed in the gonad of C. sinensis , and the potential biological functions of reproduction-related gene were also investigated in this study. The results showed that 1 013 and 427 genes were differentially expressed in the ovary and testis, respectively. KEGG enrichment analysis showed that the DEGs in the gonad were significantly clustered in progesterone-mediated oocyte maturation, cell cycle and oocyte meiosis. Further analysis showed that 23 genes were mainly involved in sex determination/differentiation, including Dmrt1 , Sox2/4/9 , Foxl2 , β-catenin and GATA-type zinc finger protein 1-like. Twenty key genes were mainly involved in the process of spermatogenesis, and five genes encode steroid biosynthesis and metabolism. Fifteen genes related to ovarian development were also identified in this study, such as Vitellogenin , MAM and LDL-receptor class A domain-containing protein 1 and Cell division cycle protein 20 homolog . Moreover, 50µg/L estradiol treatment significantly up-regulated the expression levels of CsVg in the ovary and hepatopancreas. These results highlight the genes involved in sexual determination/differentiation and gonadal development, which enhance our understanding for further studies of reproduction and breeding of C. sinensis and other marine bivalves.

Larval Fish Spatiotemporal Dynamics of Different Ecological Guilds in Yangtze Estuary - Rong Wan; Pengbo Song; Zengguang Li; Xiangyu Long; Dong Wang; Lu Zhai (Journal of Marine Science and Engineering, 2023)
Estuaries, as important fish nursery habitats, usually include a variety of larval fishes of different ecological guilds and exhibit complicated changing environmental conditions. We carried out a survey to examine the spatiotemporal dynamics of different ecological guild larval fishes and their relationships with environmental factors in the springs and summers from 2018 to 2020 in the Yangtze Estuary (China). The aims of the study were to provide detailed information on the characteristics of the larval fish assemblage and to explore the spatiotemporal variation in different ecological guild species and the effects of environmental variables on assemblage structure. More than 140,000 fish larvae from 26 families and 99 species were gathered during the six cruises, with the spring being the most prolific. The assemblage was dominated by a few species and was divided into three ecological guilds. Engraulidae was the most abundant family, followed by Cyprinidae and Gobiidae. Hemiculter bleekeri (freshwater), Pseudolaubuca sinensis (freshwater), Coilia mystus (brackish water), and Engraulis japonicas (marine) were the predominant species. Seasonal variations in larval fish assemblage structure were closely influenced by temperature, and the fluctuation in salinity mainly determined the spatial distribution of the larval fish community. Freshwater flows also played an important role in shaping the larval fish assemblage structure and dynamics. The conclusions improve the understanding of the ecological dynamics of larval fish assemblages in environmentally heterogeneous areas and may be applicable to other estuary ecosystems.

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Effects of substituting municipal waste incineration fly ash for lime on generating a bonding phase during the sintering process - Zhenqiang Jiang; Kai Dong; Hongyang Wang; Yun Zhou; Bohan Tian; Xin Li; Rong Zhu (Journal of Cleaner Production, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Role of quorum sensing-based regulation in development of anaerobic ammonium oxidation process - Jun-Hui Yang; Dong-Qi Huang; Yin-Ce Geng; Yi-Rong Ling; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

Effects and mechanism of ultrasound treatment on Chironomus kiiensis eggs - Bo-dong Liu; Hao-tao Dong; Hong-wei Rong; Rui-jian Zhang (Environmental Science and Pollution Research, 2022)

Neural mechanisms underlying empathy during alcohol abstinence: evidence from connectome-based predictive modeling - Guanzhong Yao; Luqing Wei; Ting Jiang; Hui Dong; Chris Baeken; Guo-Rong Wu (Brain Imaging and Behavior, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Study of Crack Closure Effect of Hull Plate under Low Cycle Fatigue - Qin Dong; Mengyuan Rong; Geng Xu (Journal of Marine Science and Engineering, 2022)
The crack closure phenomenon significantly influences low cycle fatigue (LCF) crack growth. The crack closure theory deems that a crack can grow only when the applied load is greater than the fatigue crack opening and closing loads. The revised crack closure theory proposed in this paper provides a new understanding of crack growth: It is no longer the range of stress intensity factor ΔK that controls the crack growth rate, but the effective stress intensity factor ΔKeff. Therefore, it is of great importance to study the crack closure phenomenon of LCF. A combination of experiments and the finite element method (FEM) was used to study the effect of overload on the crack closure effect, and the study was carried out using compact tensile (CT) specimens made of AH32 steel. The FEM was used to obtain the stress changes near the crack tip and the opening displacement changes in the crack trailing area after a single tensile overload, to study the intrinsic mechanism of overload on crack closure, and to obtain the LCF crack opening and closing loads by the nodal displacement method. The effect of overload on crack morphology was observed by using high-magnification electron microscopy in combination with testing.

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Microstructural Differences of the Cerebellum-Thalamus-Basal Ganglia-Limbic Cortex in Patients with Somatic Symptom Disorders: a Diffusion Kurtosis Imaging Study - Liao Dong; Huai-Bin Liang; Jiaxin Du; Yingying Wang; Qichen Zhou; Ziyue Xin; Yue Hu; Yi-Sheng Liu; Rong Zhao; Yuan Qiao; Chenglin Zhou; Jian-Ren Liu; et al. (The Cerebellum, 2022)

Optimization of the induction, germination, and plant regeneration system for somatic embryos in apomictic walnut (Juglans regia L.) - Hongcheng Fang; Yuhui Dong; Rui Zhou; Qingpeng Wang; Qicheng Duan; Changxi Wang; Yan Bao; Shengyi Xu; Xinya Lang; Shasha Gai; Rong Chen; Ke Qiang Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Development of Physiology Based Pharmacokinetic Model to Predict the Drug Interactions of Voriconazole and Venetoclax - Ji Dong; Shuai-bing Liu; Jony Md Rasheduzzaman; Chen-rong Huang; Li-yan Miao (Pharmaceutical Research, 2022)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Prediction of the sea buckthorn AQP gene structure and its spatiotemporal expression pattern under drought stress - Dan Zhang; Nanxiang Yang; Jiawei Dong; Cheng Wang; Qiangfeng Li; Rong Wang; Zhipeng Feng; Dejuan Xie; Guisheng Ye; Yuhua Ma (Journal of Plant Biochemistry and Biotechnology, 2022)

Renal tubule ectopic lipid deposition in diabetic kidney disease rat model and in vitro mechanism of leptin intervention - Shasha Liu; Jingjing Da; Jiali Yu; Rong Dong; Jing Yuan; Fuxun Yu; Yan Zha (Journal of Physiology and Biochemistry, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

The adsorption mechanism of CF4 on the surface of activated carbon made from peat and modified by Cu - Rong Pan; Wei Dong; Yanni Guo; Yining Tang; Jun Shang; Lei Zhou; Deliang He (Environmental Science and Pollution Research, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Sampling Designs for Monitoring Ichthyoplankton in the Estuary Area: A Case Study on Coilia mystus in the Yangtze Estuary - Xiangyu Long; Rong Wan; Zengguang Li; Dong Wang; Pengbo Song; Fan Zhang (Frontiers in Marine Science, 2022)
A fishery-independent survey can provide detailed information for fishery assessment and management. However, the sampling design for the survey on ichthyoplankton in the estuary area is still poorly understood. In this study, we developed six stratified schemes with various sample sizes, attempting to find cost-efficient sampling designs for monitoring Coilia mystus ichthyoplankton in the Yangtze Estuary. The generalized additive model (GAM) with the Tweedie distribution was used to quantify the “true” distribution of C. mystus eggs and larvae, based on the data from the fishery-independent survey in 2019–2020. The performances of different sampling designs were evaluated by relative estimation error (REE), relative bias (RB), and coefficient of variation (CV). The results indicated that appropriate stratifications with intra-stratum homogeneity and inter-stratum heterogeneity could improve precision. The stratified schemes should be divided not only between the North Branch and South Branch but between river and sea. No less than two stratifications in the South Branch could also get better performance. The sample sizes of 45–55 were considered as the cost-efficient range. Compared to other monitoring programs, monitoring ichthyoplankton in the estuary area required a more complex stratification and a higher resolution sampling. The design ideology and optimization methodology in our study would provide references to sampling designs for ichthyoplankton in the estuary area.

Predictive value of monocyte to HDL cholesterol ratio for stroke-associated pneumonia in patients with acute ischemic stroke - Yaming Sun; Juan Lu; Danni Zheng; Jufen Qian; Hongxin Zhang; Dong Xing; Fengdan Rong; Yongjun Cao; Chun-Feng Liu; Shoujiang You (Acta Neurologica Belgica, 2021)

The Non-stationary Environmental Effects on Spawning Habitat of Fish in Estuaries: A Case Study of Coilia mystus in the Yangtze Estuary - Dong Wang; Rong Wan; Zengguang Li; Junbo Zhang; Xiangyu Long; Pengbo Song; Lu Zhai; Shuo Zhang (Frontiers in Marine Science, 2021)
The estuarine areas provide necessary spawning habitat, nursing habitat, and migratory for a variety of fishes and the environmental conditions are of significant heterogeneity. Coilia mystus is the key commercial fish that spawns in the Yangtze Estuary and the yield has declined sharply in the past 30 years. In order to understand the spawning habitat selection mechanism of C. mystus , the geographically weighted regression (GWR) model was applied to explore the non-stationary effect of environmental variables [e.g., the sea surface temperature (SST) and the sea surface salinity (SSS)] and geographical variables [e.g., the distance to the coast (DTC) and the depth (DEP) of water] on the egg density distribution of C. mystus . The data were derived from the spring and summer ichthyoplankton surveys carried out from 2019 to 2020 in the Yangtze Estuary, China. The GWR model results showed that the key variables in different seasons had spatial non-stationary effects on the distribution of spawning habitat of C. mystus , which were mainly caused by regional rise in temperature and saltwater intrusion of the South Branch. In the spring, the SSS, the DTC, and the DEP were the main impact factors and saltwater intrusion in the South Branch might lead to the trend that the spawning habitat moved further upstream to the Changxing Island. The SST was most important in the summer and the relatively lower SST was more crucial in the spawning habitat selection than the DTC and the DEP. The GWR model performed well in the study of C. mystus potential spawning habitat in the Yangtze Estuary. We recommend that more attention should be paid in regional variation of environmental factors to explore fish potential spawning habitat in the estuarine areas.

Mixing overstory tree- and understory fern-derived dissolved organic carbon produces non-additive effects on biodegradation in subtropical forests of southern China - Su-Li Li; Zhi Zheng; Yi-Dong Ding; Jia-Wen Xu; Rong Mao (Plant and Soil, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Tree mycorrhizal effect on litter-leached DOC amounts and biodegradation is highly dependent on leaf habits in subtropical forests of southern China - Yi-Dong Ding; Xin-Yi Xie; Jing-Hao Ji; Qian-Qian Li; Jia-Wen Xu; Rong Mao (Journal of Soils and Sediments, 2021)

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer - Li-rong Yan; Han-xi Ding; Shi-xuan Shen; Xiao-dong Lu; Yuan Yuan; Qian Xu (Functional & Integrative Genomics, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Efficient separation and recovery of Re(VII) from Re/U bearing acidic solutions using aminotriazole modified cellulose microsphere adsorbents - Di Wen; Rong Hua; Zhen Dong; Kangjun Xie; Wei Qi; Long Zhao (Environmental Science and Pollution Research, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Reconstruction method of irregular seismic data with adaptive thresholds based on different sparse transform bases - Hu Zhao; Tun Yang; Yu-Dong Ni; Xing-Gang Liu; Yin-Po Xu; Yi-Lei Zhang; Guang-Rong Zhang (Applied Geophysics, 2021)

Neuroprotective Effect of Phthalide Derivative CD21 against Ischemic Brain Injury:Involvement of MSR1 Mediated DAMP peroxiredoxin1 Clearance and TLR4 Signaling Inhibition - Xiao Zou; Xiao-Jia Yang; Yu-Miao Gan; Dong-Ling Liu; Chu Chen; Wei Duan; Jun-Rong Du (Journal of Neuroimmune Pharmacology, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Triaxial Compression Testing at Constant and Reducing Confining Pressure for the Mechanical Characterization of a Specific Type of Sandstone - Jiu-chang Zhang; Zhi-nan Lin; Bo Dong; Rong-xin Guo (Rock Mechanics and Rock Engineering, 2021)

Phytoremediation of Cadmium Contaminated Soil: Impacts on Morphological Traits, Proline Content and Stomata Parameters of Sweet Sorghum Seedlings - Xicun Dong; Yan Chang; Rong Zheng; Xueqiang Wang; Xia Yan; Xiao-Fei Ma (Bulletin of Environmental Contamination and Toxicology, 2021)

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

Benefit of Dietary Supplementation with Bacillus subtilis BYS2 on Growth Performance, Immune Response, and Disease Resistance of Broilers - Yunxiang Dong; Rong Li; Yu Liu; Lianying Ma; Jihua Zha; Xibo Qiao; Tongjie Chai; Bo Wu (Probiotics and Antimicrobial Proteins, 2020)

Physiological and transcriptional response to heat stress in heat-resistant and heat-sensitive maize (Zea mays L.) inbred lines at seedling stage - De-Chuan Wu; Jia-Fei Zhu; Zhong-Ze Shu; Wei Wang; Cheng Yan; Shan-Bin Xu; De-Xiang Wu; Cheng-Yu Wang; Zhao-rong Dong; Genlou Sun (Protoplasma, 2020)

Influence of soil moisture content on pullout properties of Hippophae rhamnoides Linn. roots - Chao-bo Zhang; Ya-ting Liu; Dong-rong Li; Jing Jiang (Journal of Mountain Science, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Water and salt stresses do not trigger bottom-up effects on plant-mediated indirect interactions between a leaf chewer and a sap-feeder - Yong-Cheng Dong; Zhi-Jian Wang; Rong-Yan Bu; Hui-Jie Dai; Li-Jun Zhou; Peng Han; Edwige Amiens-Desneux; Philippe Bearez; Nicolas Desneux (Journal of Pest Science, 2020)

Addition of oyster shell to enhance organic matter degradation and nitrogen conservation during anaerobic digestate composting - Ming-Yi Lu; Xiao-Shuang Shi; Xu Li; Shu-Juan Lian; Dong-Yan Xu; Rong-Bo Guo (Environmental Science and Pollution Research, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Ferulic Acid Ameliorates MPP+/MPTP-Induced Oxidative Stress via ERK1/2-Dependent Nrf2 Activation: Translational Implications for Parkinson Disease Treatment - Xu Li; Jing Zhang; Hua Rong; Xiaojie Zhang; Miaoxian Dong (Molecular Neurobiology, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

CU06-1004 (endothelial dysfunction blocker) ameliorates astrocyte end-feet swelling by stabilizing endothelial cell junctions in cerebral ischemia/reperfusion injury - Dong Young Kim; Haiying Zhang; Songyi Park; Yeaji Kim; Cho-Rong Bae; Young-Myeong Kim; Young-Guen Kwon (Journal of Molecular Medicine, 2020)
Cerebral ischemia, or stroke, is widespread leading cause of death and disability. Surgical and pharmacological interventions that recover blood flow are the most effective treatment strategies for stroke patients. However, restoring the blood supply is accompanied by severe reperfusion injury, with edema and astrocyte end-feet disruption. Here, we report that the oral administration of CU06-1004 (previously Sac-1004), immediately after onset of ischemia/reperfusion (I/R), ameliorated cerebral damage. CU06-1004 stabilized blood‑brain barrier by inhibiting the disruption of the tight junction-related protein zona occludens-1 and the cortical actin ring in endothelial cells (ECs) after I/R. Interestingly, CU06-1004 significantly suppressed astrocyte end-feet swelling following I/R, by reducing aquaporin 4 and connexin 43 levels, which mediates swelling. Furthermore, the degradation of β1-integrin and β-dystroglycan, which anchors to the cortical actin ring in ECs, was inhibited by CU06-1004 administration after I/R. Consistently, CU06-1004 administration following I/R also suppressed the loss of laminin and collagen type IV, which bind to the cortical actin ring anchoring proteins. Unlike the protective effects of CU06-1004 in ECs, astrocyte viability and proliferation were not directly affected. Taken together, our observations suggest that CU06-1004 inhibits I/R-induced cerebral edema and astrocyte end-feet swelling by maintaining EC junction stability. Key messages • CU06-1004 ameliorates I/R-induced cerebral injury. • EC junction integrity was stabilized by CU06-1004 treatment after I/R. • CU06-1004 reduces astrocyte end-feet swelling following I/R. • EC junction stability affects astrocyte end-feet structure maintenance after I/R.

Simulation of the landform change process on a purple soil slope due to tillage erosion and water erosion using UAV technology - Chao Yang; Zheng-an Su; Jian-rong Fan; Hai-dong Fang; Liang-tao Shi; Jian-hui Zhang; Zhou-yao He; Tao Zhou; Xiao-yi Wang (Journal of Mountain Science, 2020)

Response of individual sizes and spatial patterns of Deyeuxia angustifolia to increasing water level gradient in a freshwater wetland - Heng Ren; Fu-xi Shi; Rong Mao; Yue-dong Guo; Wen-zhi Zhao (Environmental Science and Pollution Research, 2020)

Biofertilizer application triggered microbial assembly in microaggregates associated with tomato bacterial wilt suppression - Menghui Dong; Mengli Zhao; Zongzhuan Shen; Xuhui Deng; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Qirong Shen (Biology and Fertility of Soils, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Estradiol regulates the expression of CD45 splicing isoforms in lymphocytes - Tianwei Zhang; Zhaoxia Dong; Haitao Cai; Ju Rong; Zhongjing Su (Molecular Biology Reports, 2020)

Blumea hunanensis (Asteraceae: Inuleae), a new species from Hunan, China - Lin-Dong Duan; Yun Lin; Zhi-Rong Yang; Zhen Lu (Kew Bulletin, 2020)

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

Bidirectional Regulatory Mechanisms of Jaceosidin on Mitochondria Function: Protective Effects of the Permeability Transition and Damage of Membrane Functions - Wen-Rong Fu; Ji-Lei Chen; Xue-Yi Li; Jia-Xin Dong; Yi Liu (The Journal of Membrane Biology, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Identifying the Design Alternatives and Flow Interference of Tuna Purse Seine by the Numerical Modelling Approach - Cheng Zhou; Liuxiong Xu; Hao Tang; Fuxiang Hu; Pingguo He; Taisei Kumazawa; Xuefang Wang; Rong Wan; Shuchuang Dong (Journal of Marine Science and Engineering, 2019)
Dynamic responses of tuna purse seine to currents were numerically studied with regard to the vertical subsidence and global load distribution, and determinant attributes were identified. We rebuilt the submerged geometry of a purse seine net using the lumped mass method with hydrodynamic coefficients obtained from measurements of the prototype material, as well as a mesh grouping method, which corrects the twine diameter and netting material density for the equivalent net by introducing the compensation coefficient. Uneven tension distribution showed that it was vulnerable to high loads in the bunt area at shooting and along the lead line at pursing. High loads were present at the convex sections of net circles in the direction of the current. Higher shooting speeds resulted in well-balanced sinking, while a reduced hanging ratio of netting panels was beneficial to faster sinking. While large mesh sizes reduce water resistance and increase sinking velocity, extensive use should be cautioned in terms of the sensibility to stress. Comparing two options of different proportions of large-mesh panels, mesh sizes doubled for 15 strips versus 5 strips, suggesting that the 15 strip option would pose a higher risk of strand vulnerability, while the 5 strip option may be a more balanced alternative with a lower mesh density and a lower mesh stress.

Urinary Metal Concentrations and the Incidence of Hypertension Among Adult Residents Along the Yangtze River, China - Qi Zhong; Chun-xiao Jiang; Chi Zhang; Qian Zhang; Qi-rong Qin; Xiao-dong Wang; Fen Huang (Archives of Environmental Contamination and Toxicology, 2019)

Network parameters quantify loss of assemblage structure in human‐impacted lake ecosystems - Rong Wang; John A. Dearing; C. Patrick Doncaster; Xiangdong Yang; Enlou Zhang; Peter G. Langdon; Hui Yang; Xuhui Dong; Zhujun Hu; Min Xu; Yanjie Zhao; Ji Shen (Global Change Biology, 2019)
Lake biodiversity is an incomplete indicator of exogenous forcing insofar as it ignores underlying deformations of community structure. Here, we seek a proxy for deformation in a network of diatom assemblages comprising 452 species in 273 lakes across China. We test predictions from network theory that nodes of similar type will tend to self‐organize in an unstressed system to a positively skewed frequency distribution of nodal degree. The empirical data reveal shifts in the frequency distributions of species associations across regions, from positive skew in lakes in west China with a history of low human impacts, to predominantly negative skew amongst lakes in highly disturbed regions in east China. Skew values relate strongly to nutrient loading from agricultural activity and urbanization, as measured by total phosphorus in lake water. Reconstructions through time show that positive skew reduces with temporal intensification of human impacts in the lake and surrounding catchments, and rises as lakes recover from disturbance. Our study illustrates how network parameters can track the loss of aquatic assemblage structure in lakes associated with human pressures.

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

Involvement of mitochondrial dysfunction in hepatotoxicity induced by Ageratina adenophora in mice - Wei Sun; Chao-rong Zeng; Dong Yue; Yan-chun Hu (Journal of Zhejiang University-SCIENCE B, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

The response of metabolically active Clostridium community to initial pH shift is closely correlated with microbial Fe(III) reduction in flooded paddy soils - Lina Li; Zhi Qu; Baoli Wang; Rong Jia; Dong Qu (Journal of Soils and Sediments, 2019)

Identification of Carassius auratus gibelio liver cell proteins interacting with the GABAA receptor γ2 subunit using a yeast two-hybrid system - Rong-Rong Ma; Jing Sun; Wen-Hong Fang; Ya-Ping Dong; Ji-Ming Ruan; Xian-Le Yang; Kun Hu (Fish Physiology and Biochemistry, 2019)

A new actinomycin Z analogue with an additional oxygen bridge between chromophore and β -depsipentapeptide from Streptomyces sp. KIB-H714 - Miao Dong; Pei Cao; Ya-Tuan Ma; Jianying Luo; Yijun Yan; Rong-Tao Li; Sheng-Xiong Huang (Natural Product Research, 2019)

A mutation in class III homeodomain-leucine zipper (HD-ZIP III) transcription factor results in curly leaf (cul) in cucumber (Cucumis sativus L.) - Fuxi Rong; Feifan Chen; Li Huang; Jiayu Zhang; Chaowen Zhang; Dong Hou; Zhihui Cheng; Yiqun Weng; Peng Chen; Yuhong Li (Theoretical and Applied Genetics, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Arctic Climate Changes Based on Historical Simulations (1900‒2013) with the CAMS-CSM - Ting Wei; Jian Li; Xinyao Rong; Wenjie Dong; Bingyi Wu; Minghu Ding (Journal of Meteorological Research, 2018)

Correction to: Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji‑Dong Ya; Zhi‑Xiang Yu; Yong-Qiong Yang; Shu‑Dong Zhang; Zhi‑Rong Zhang; Jie Cai; Jun‑Bo Yang; Wen‑Bin Yu (Conservation Genetics Resources, 2018)

Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji-Dong Ya; Zhi-Xiang Yu; Yan-Qiong Yang; Shu-Dong Zhang; Zhi-Rong Zhang; Jie Cai; Jun-Bo Yang; Wen-Bin Yu (Conservation Genetics Resources, 2018)

Cretaceous A-type volcanic–intrusive rocks and simultaneous mafic rocks along the Gan-Hang Tectonic Belt, Southeast China: petrogenesis and implications for the transition of crust–mantle interaction - Hong-Zuo Wang; Pei-Rong Chen; Kai-Xing Wang; Hong-Fei Ling; Jun-Qi Wu; Jiang-Wei Tang; You-Dong Zhao (International Geology Review, 2018)

Mid–Late Cretaceous igneous activity in South China: the Qianjia example, Hainan Island - Sai-Jun Sun; Li-Peng Zhang; Rong-Qing Zhang; Xing Ding; Hong-Li Zhu; Zhao-Feng Zhang; Wei-Dong Sun (International Geology Review, 2018)

First report of tomato yellow Leaf curl virus and cucumber mosaic virus infecting Huoxiang (Agastache rugosa) in CHINA - Rong Wang; Yong Li; Jia-Li Dong; Wan-Long Ding (Journal of Plant Pathology, 2018)

GDC-0152-induced autophagy promotes apoptosis in HL-60 cells - Liang Peiqi; Hu Rong; Dong Hongming; Liu Zhuogang; Jiang Wei; Miao Miao (Molecular and Cellular Biochemistry, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Complete nucleotide sequence of a new carlavirus in chrysanthemums in China - Rong Wang; Jiali Dong; Zhen Wang; Tao Zhou; Yong Li; Wanlong Ding (Archives of Virology, 2018)

Inhibitory Effect of Vaginal Lactobacillus Supernatants on Cervical Cancer Cells - Ke-Di Wang; Dong-Jiang Xu; Bao-Ya Wang; Dong-Hui Yan; Zhi Lv; Jian-Rong Su (Probiotics and Antimicrobial Proteins, 2018)

Studies of the Interaction of Influenza Virus RNA Polymerase PAN with Endonuclease Inhibitors - Li-hua Dong; Xiao-rong Cao (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Posterior circulation involvement in pediatric and adult patients with moyamoya disease: a single center experience in 574 patients - Meng Zhao; Dong Zhang; Shuo Wang; Yan Zhang; Rong Wang; Xiaofeng Deng; Jizong Zhao (Acta Neurologica Belgica, 2018)

Protective effect of the total flavonoids from Apocynum venetum L. on carbon tetrachloride-induced hepatotoxicity in vitro and in vivo - Wei Zhang; Zheng Dong; Xiujuan Chang; Cuihong Zhang; Guanghua Rong; Xudong Gao; Zhen Zeng; Chunping Wang; Yan Chen; Yihui Rong; Jianhui Qu; Ze Liu; et al. (Journal of Physiology and Biochemistry, 2018)

The Effect of Bisphenol A on Growth, Morphology, Lipid Peroxidation, Antioxidant Enzyme Activity, and PS II in Cylindrospermopsis raciborskii and Scenedesmus quadricauda - Rong Xiang; Junqiong Shi; Yi Yu; Hongbo Zhang; Congcong Dong; Yanjun Yang; Zhongxing Wu (Archives of Environmental Contamination and Toxicology, 2018)

Simultaneous determination of three pesticides and their metabolites in unprocessed foods using ultraperformance liquid chromatography-tandem mass spectrometry - Lili Rong; Xiaohu Wu; Jun Xu; Fengshou Dong; Xingang Liu; Xinglu Pan; Pengqiang Du; Dongmei Wei; Yongquan Zheng (Food Additives & Contaminants: Part A, 2018)

Enhanced iron(III) reduction following amendment of paddy soils with biochar and glucose modified biochar - Rong Jia; Lina Li; Dong Qu; Nana Mi (Environmental Science and Pollution Research, 2018)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Possible Effects of Electric Fields on a Pair of Spherical Cells - Yu Zheng; Jing Xue; Yang Gao; Lei Dong; Jun-rong Dou; Wei Ma (The Journal of Membrane Biology, 2017)

Periostin promotes ectopic osteogenesis of CTLA4-modified bone marrow mesenchymal stem cells - Fei Zhang; Zhigang Rong; Zhengdong Wang; Zehua Zhang; Dong Sun; Shiwu Dong; Jianzhong Xu; Fei Dai (Cell and Tissue Research, 2017)

A Review of Geophysical Exploration Technology for Mine Water Disaster in China: Applications and Trends - Tuo Lu; Sheng-dong Liu; Bo Wang; Rong-xin Wu; Xiong-wu Hu (Mine Water and the Environment, 2017)

The levels of DNGR-1 and its ligand-bearing cells were altered after human and simian immunodeficiency virus infection - Wen-Rong Yao; Dong Li; Lei Yu; Feng-Jie Wang; Hui Xing; Gui-Bo Yang (Immunologic Research, 2017)

Assimilation of total lightning data using the three-dimensional variational method at convection-allowing resolution - Rong Zhang; Yijun Zhang; Liangtao Xu; Dong Zheng; Wen Yao (Journal of Meteorological Research, 2017)

Globular adiponectin inhibits leptin-stimulated esophageal adenocarcinoma cell proliferation via adiponectin receptor 2-mediated suppression of UHRF1 - Jun Wang; Yan Cheng; Xiaoran Yin; Jie Wu; Yumei Luo; Jing Wu; Jia Di; Dong Liu; Yahui Huang; Rong Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2017)

Development of a Time-Resolved Fluorescence Immunoassay for the Diagnosis of Hepatocellular Carcinoma Based on the Detection of Glypican-3 - Juan-Juan Chen; Chun-Mei Xie; Cong-Rong Wang; Yong Wan; Zhi-Ning Dong; Ming Li; Wei-Wen Xu (Journal of Fluorescence, 2017)

Spatial distribution of turbulent mixing in the upper ocean of the South China Sea - Xiao-Dong Shang; Chang-Rong Liang; Gui-Ying Chen (Ocean Science, 2017)
The spatial distribution of the dissipation rate (ε) and diapycnal diffusivity (κ) in the upper ocean of the South China Sea (SCS) is presented from a measurement program conducted from 26 April to 23 May 2010. In the vertical distribution, the dissipation rates below the surface mixed layer were predominantly high in the thermocline where shear and stratification were strong. In the regional distribution, high dissipation rates and diapycnal diffusivities were observed in the region to the west of the Luzon Strait, with an average dissipation rate and diapycnal diffusivity of 8.3 × 10−9 W kg−1 and 2.7 × 10−5 m2 s−1, respectively, almost 1 order of magnitude higher than those in the central and southern SCS. In the region to the west of the Luzon Strait, the water column was characterized by strong shear and weak stratification. Elevated dissipation rates (ε > 10−7 W kg−1) and diapycnal diffusivities (κ > 10−4 m2 s−1), induced by shear instability, occurred in the water column. In the central and southern SCS, the water column was characterized by strong stratification and weak shear and the turbulent mixing was weak. Internal waves and internal tides generated near the Luzon Strait are expected to make a dominant contribution to the strong turbulent mixing and shear in the region to the west of the Luzon Strait. The observed dissipation rates were found to scale positively with the shear and stratification, which were consistent with the MacKinnon–Gregg model used for the continental shelf but different from the Gregg–Henyey scaling used for the open ocean.

Association between hyperhomocysteinemia and stroke with atherosclerosis and small artery occlusion depends on homocysteine metabolism-related vitamin levels in Chinese patients with normal renal function - Guan-Hui Wu; Fan-Zhen Kong; Xiao-Feng Dong; De-Feng Wu; Qian-Zhu Guo; Ai-Rong Shen; Qing-Zhang Cheng; Wei-Feng Luo (Metabolic Brain Disease, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Population transcriptomes reveal synergistic responses of DNA polymorphism and RNA expression to extreme environments on the Qinghai–Tibetan Plateau in a predatory bird - Shengkai Pan; Tongzuo Zhang; Zhengqin Rong; Li Hu; Zhongru Gu; Qi Wu; Shanshan Dong; Qiong Liu; Zhenzhen Lin; Lucia Deutschova; Xinhai Li; Andrew Dixon; et al. (Molecular Ecology, 2017)
Low oxygen and temperature pose key physiological challenges for endotherms living on the Qinghai–Tibetan Plateau ( QTP ). Molecular adaptations to high‐altitude living have been detected in the genomes of Tibetans, their domesticated animals and a few wild species, but the contribution of transcriptional variation to altitudinal adaptation remains to be determined. Here we studied a top QTP predator, the saker falcon, and analysed how the transcriptome has become modified to cope with the stresses of hypoxia and hypothermia. Using a hierarchical design to study saker populations inhabiting grassland, steppe/desert and highland across Eurasia, we found that the QTP population is already distinct despite having colonized the Plateau cDNA level, but of only seventeen genes identified, three function in hypoxia and four in immune response. Our results show a significant role for RNA transcription: 50% of upregulated transcription factors were related to hypoxia responses, differentiated modules were significantly enriched for oxygen transport, and importantly, divergent EPAS 1 functional variants with a refined co‐expression network were identified. Conservative gene expression and relaxed immune gene variation may further reflect adaptation to hypothermia. Our results exemplify synergistic responses between DNA polymorphism and RNA expression diversity in coping with common stresses, underpinning the successful rapid colonization of a top predator onto the QTP . Importantly, molecular mechanisms underpinning highland adaptation involve relatively few genes, but are nonetheless more complex than previously thought and involve fine‐tuned transcriptional responses and genomic adaptation.

Observations of the turbulent kinetic energy dissipation rate in the upper central South China Sea - Chang-Rong Liang; Gui-Ying Chen; Xiao-Dong Shang (Ocean Dynamics, 2017)

Changes and relations of photosynthesis and iron cycling in anoxic paddy soil amended with high concentrations of sulfate - Qin Chen; Rong Jia; Dong Qu; Ming Li (Environmental Science and Pollution Research, 2017)

The dynamics of landscape-scale ecological connectivity based on least-cost model in Dongshan Island, China - Li-yun Wu; Dong-jin He; Wei-bin You; Zhi-rong Ji; Yong Tan; Li-li Zhao (Journal of Mountain Science, 2017)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

Antioxidant and hyaluronidase inhibitory activities of diverse phenolics in Phyllanthus emblica - Min Xu; Hong-Tao Zhu; Rong-Rong Cheng; Dong Wang; Chong-Ren Yang; Takashi Tanaka; Isao Kouno; Ying-Jun Zhang (Natural Product Research, 2016)

EGFL7-overexpressing epidermal stem cells promotes fibroblast proliferation and migration via mediating cell adhesion and strengthening cytoskeleton - Rong-Hua Yang; Shao-Hai Qi; Shu-Bin Ruan; Ze-Peng Lin; Yan Lin; Feng-Gang Zhang; Xiao-Dong Chen; Ju-Lin Xie (Molecular and Cellular Biochemistry, 2016)

DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Early warning of critical transitions in biodiversity from compositional disorder - C. Patrick Doncaster; Vasthi Alonso Chávez; Clément Viguier; Rong Wang; Enlou Zhang; Xuhui Dong; John A. Dearing; Peter G. Langdon; James G. Dyke (Ecology, 2016)
Global environmental change presents a clear need for improved leading indicators of critical transitions, especially those that can be generated from compositional data and that work in empirical cases. Ecological theory of community dynamics under environmental forcing predicts an early replacement of slowly replicating and weakly competitive “canary” species by slowly replicating but strongly competitive “keystone” species. Further forcing leads to the eventual collapse of the keystone species as they are replaced by weakly competitive but fast‐replicating “weedy” species in a critical transition to a significantly different state. We identify a diagnostic signal of these changes in the coefficients of a correlation between compositional disorder and biodiversity. Compositional disorder measures unpredictability in the composition of a community, while biodiversity measures the amount of species in the community. In a stochastic simulation, sequential correlations over time switch from positive to negative as keystones prevail over canaries, and back to positive with domination of weedy species. The model finds support in empirical tests on multi‐decadal time series of fossil diatom and chironomid communities from lakes in China. The characteristic switch from positive to negative correlation coefficients occurs for both communities up to three decades preceding a critical transition to a sustained alternate state. This signal is robust to unequal time increments that beset the identification of early‐warning signals from other metrics.

A new flavonoid glycoside from Elsholtzia bodinieri - Jin-Dong Zhong; Yue Feng; Hong-Mei Li; Xue-Shan Xia; Rong-Tao Li (Natural Product Research, 2016)

Metagenomic analysis shows diverse, distinct bacterial communities in biofilters among different marine recirculating aquaculture systems - Zhitao Huang; Rong Wan; Xiefa Song; Ying Liu; Eric Hallerman; Dengpan Dong; Jieming Zhai; Hesen Zhang; Liyuan Sun (Aquaculture International, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

A Fluorescence Immunochromatographic Assay Using Europium (III) Chelate Microparticles for Rapid, Quantitative and Sensitive Detection of Creatine Kinase MB - Xiao-Hong Lai; Rong-Liang Liang; Tian-Cai Liu; Zhi-Ning Dong; Ying-Song Wu; Lin-Hai Li (Journal of Fluorescence, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Soil washing in combination with homogeneous Fenton-like oxidation for the removal of 2,4,4′-trichlorodiphenyl from soil contaminated with capacitor oil - Xiao-Hong Ma; Ling Zhao; Zhi-Rong Lin; Yuan-Hua Dong (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A novel acetylcholinesterase inhibitor and calcium channel blocker SCR-1693 improves Aβ25–35-impaired mouse cognitive function - Zhengping Zhang; Rong Chen; Wenji An; Chunmei Wang; Gaoyong Liao; Xiaoliang Dong; Aijing Bi; Zhimin Yin; Lan Luo (Psychopharmacology, 2016)

The effect of different genome and cytoplasm on meiotic pairing in maize newly synthetic polyploids - Mingjun Cheng; Mingmin Zheng; Shipeng Yang; Yang Li; Xingchun Dong; Jing Li; Rulong Sun; Huaxiong Li; Shufeng Zhou; Yuanqi Wu; Tingzhao Rong; Qilin Tang (Euphytica, 2016)
Allopolyploidization plays the special role in the evolution of many crops. Moreover, the evolution in early stage of some allopolyploidization events is predicted to be effected by nuclear-cytoplasmic interactions. Maize and teosintes are well model system for study of genetic recombination in allopolyploidization. In order to investigate the effects of genome organization and cytoplasm on genome evolution in newly synthesized allopolyploids (neoallopolyploids), a series of neoallopolyploids were produced by reciprocal crosses of maize and Zea perennis . By using dual-color genomic in situ hybridization, intra- and intergenomic meiosis pairing of these polyploids were quantified and compared with regard to its genome organization and cytoplasm background. In the four neoallopolyploids, the stability of maize genome is consistently lower than that of Z. perennis genome. Additional, the stability of maize genome is affected by genome ploidy. The cytoplasm, genome composition and their interaction do have the special role in chromosome paring and the meiosis behaviors in Zea allopolyploids vary significantly and showed non-diploidization. Z. perennis cytoplasm may give a relatively relaxed environment for maize genome.

The meso-mechanism study of gypsum rock weakening in brine solutions - Wei Dong Yu; Wei Guo Liang; Yan Rong Li; Yan Mei Yu (Bulletin of Engineering Geology and the Environment, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Preferable procedure for the screening of syphilis in clinical laboratories in China - Ke-Di Wang; Dong-Jiang Xu; Jian-Rong Su (Infectious Diseases, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Practical considerations for the segmented-flow analysis of nitrate and ammonium in seawater and the avoidance of matrix effects - Tae Keun Rho; Stephen Coverly; Eun-Soo Kim; Dong-Jin Kang; Sung-Hyun Kahng; Tae-Hee Na; Sung-Rok Cho; Jung-Moo Lee; Cho-Rong Moon (Ocean Science Journal, 2015)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

RETRACTED ARTICLE: Correlation of Promoter Methylation in the MGMT Gene with Glioma Risk and Prognosis: a Meta-Analysis - Xiang Dong; Rong-Yao Liu; Wei-Dong Chen (Molecular Neurobiology, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Interlocking Intramedullary Nails in Fracture Treatment - Xiao Ouyang; Jing Rong Wang; Shi Dong Hong; Feng Xin; Lin Wang; Xiao Wei Yang; Jian Wang (Cell Biochemistry and Biophysics, 2015)

Compositions of fatty acids and phytosterols of plant-based oils and their associations with anti-oxidative capacity: Application of principal component analysis - Jae Kyeom Kim; Ho-Jeong Lim; Dong-Hoon Shin; Cho Rong Kim; Mi-Jeong Kim; Jiyeon Chun; Eui-Cheol Shin (Horticulture, Environment, and Biotechnology, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Multiple Mesozoic magma processes formed the 240–185 Ma composite Weishan pluton, South China: evidence from geochronology, geochemistry, and Sr-Nd isotopes - Xing Ding; Wei-Dong Sun; Wei-Feng Chen; Pei-Rong Chen; Tao Sun; Sai-Jun Sun; Chiou-Ting Lin; Fu-Kun Chen (International Geology Review, 2015)

Erratum to: pH shift-mediated dehydrogenation and hydrogen production are responsible for microbial iron(III) reduction in submerged paddy soils - Rong Jia; Li-Na Li; Dong Qu (Journal of Soils and Sediments, 2015)

Altered Functional Connectivity Patterns of the Insular Subregions in Psychogenic Nonepileptic Seizures - Rong Li; Kai Liu; Xujing Ma; Zhiqiang Li; Xujun Duan; Dongmei An; Qiyong Gong; Dong Zhou; Huafu Chen (Brain Topography, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

pH shift-mediated dehydrogenation and hydrogen production are responsible for microbial iron(III) reduction in submerged paddy soils - Rong Jia; Li-Na Li; Dong Qu (Journal of Soils and Sediments, 2015)

Determination of tumorigenic Agrobacterium density in soil by real-time PCR assay and its effect on crown gall disease severity - Qian Li; Rong-Jun Guo; Shi-Dong Li; Shi-Fang Li; Hong-Qing Wang (European Journal of Plant Pathology, 2015)

Polycyclic aromatic hydrocarbons associated with total suspended particles and surface soils in Kunming, China: distribution, possible sources, and cancer risks - Xiaoxia Yang; Dong Ren; Wenwen Sun; Xiaoman Li; Bin Huang; Rong Chen; Chan Lin; Xuejun Pan (Environmental Science and Pollution Research, 2015)

Detection of brown planthopper infestation based on SPAD and spectral data from rice under different rates of nitrogen fertilizer - Jian-Rong Huang; Jia-Yi Sun; Huai-Jian Liao; Xiang-Dong Liu (Precision Agriculture, 2015)

Association analyses of FGFR2 gene polymorphisms with femoral neck bone mineral density in Chinese Han population - Shan-Shan Dong; Tie-Lin Yang; Han Yan; Zheng-Qin Rong; Jia-Bin Chen; Ruo-Han Hao; Xiao-Feng Chen; Yan Guo (Molecular Genetics and Genomics, 2015)

Bacteriological and virulence study of a Mycobacterium chimaera isolate from a patient in China - Guan Liu; Su-Ting Chen; Xia Yu; Yu-Xun Li; Ying Ling; Ling-Ling Dong; Su-Hua Zheng; Hai-Rong Huang (Antonie van Leeuwenhoek, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Tree architecture varies with forest succession in evergreen broad-leaved forests in Eastern China - Xiao-Dong Yang; En-Rong Yan; Scott X. Chang; Liang-Jun Da; Xi-Hua Wang (Trees, 2015)

Impacts of shape and height of upstream roof on airflow and pollutant dispersion inside an urban street canyon - Yuan-dong Huang; Wen-rong He; Chang-Nyung Kim (Environmental Science and Pollution Research, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Halovenus rubra sp. nov., Isolated from Salted Brown Alga Laminaria - Dong Han; Wen-Jiao Zhang; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2015)

Effects of exogenous NO on the growth, mineral nutrient content, antioxidant system, and ATPase activities of Trifolium repens L. plants under cadmium stress - Shi-Liang Liu; Rong-Jie Yang; Ming-Dong Ma; Fang Dan; Yan Zhao; Pan Jiang; Mao-Hua Wang (Acta Physiologiae Plantarum, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Research and experimental testing of a new kind electrokinetic logging tool - Feng-Bo Li; Xiao-Dong Ju; Wen-Xiao Qiao; Jun-Qiang Lu; Bai-Rong Men (Applied Geophysics, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Serological report of pandemic and seasonal human influenza virus infection in dogs in southern China - Xin Yin; Fu-Rong Zhao; Dong-Hui Zhou; Ping Wei; Hui-Yun Chang (Archives of Virology, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Analysis on the association between PPARα/γ polymorphisms and lipoprotein(a) in a Chinese Han population - Hui-Jian Xie; Bo Hai; Ming Wu; Qiu Chen; Meng-Meng Liu; Chen Dong; Zhi-Rong Guo (Molecular Genetics and Genomics, 2014)

Halopenitus salinus sp. nov., isolated from the brine of salted brown alga Laminaria - Dong Han; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2014)

Potential Effects of Mina53 on Tumor Growth in Human Pancreatic Cancer - Xiao-ping Tan; Wei-guo Dong; Qing Zhang; Zi-rong Yang; Xiao-fei Lei; Ming-hua Ai (Cell Biochemistry and Biophysics, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Attenuation of Reserpine-Induced Pain/Depression Dyad by Gentiopicroside Through Downregulation of GluN2B Receptors in the Amygdala of Mice - Shui-bing Liu; Rong Zhao; Xu-sheng Li; Hong-ju Guo; Zhen Tian; Nan Zhang; Guo-dong Gao; Ming-gao Zhao (NeuroMolecular Medicine, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Molecular characterisation and expression profiling of the ENO1 gene in the ovarian follicle of the Sichuan white goose - Bo Kang; Dong Mei Jiang; Lin Bai; Hui He; Rong Ma (Molecular Biology Reports, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Overexpression of S100P promotes colorectal cancer metastasis and decreases chemosensitivity to 5-FU in vitro - Lei Dong; Fule Wang; Xiaona Yin; Ling Chen; Gang Li; Feiyan Lin; Wuhua Ni; Jianbo Wu; Rong Jin; Lei Jiang (Molecular and Cellular Biochemistry, 2014)

Gene expression profiles in intracranial aneurysms - Lanbing Yu; Jinghan Fan; Shuo Wang; Dong Zhang; Rong Wang; Yuanli Zhao; Jizong Zhao (Neuroscience Bulletin, 2014)

Sorption of cyromazine on humic acid: Effects of pH, ionic strength and foreign ions - Ling Zhao; Zhi-rong Lin; Yuan-hua Dong (Environmental Science and Pollution Research, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

A method for monitoring the on-orbit performance of a satellite sensor infrared window band using oceanic drifters - Min Min; Yong Zhang; Zhiguo Rong; Lixin Dong (International Journal of Remote Sensing, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Perceptual quality assessment of SAR image compression - Anzhou Hu; Rong Zhang; Dong Yin; Yuan Chen; Xin Zhan (International Journal of Remote Sensing, 2013)

The expression and regulation of DFNA5 in human hepatocellular carcinoma DFNA5 in hepatocellular carcinoma - Cong-Jun Wang; Lin Tang; Dong-Wei Shen; Chao Wang; Qiong-Ying Yuan; Wei Gao; Yong-Kun Wang; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Characteristics of rainfall erosivity based on tropical rainfall measuring mission data in Tibet, China - Jian-rong Fan; Yang Chen; Dong Yan; Fen-fen Guo (Journal of Mountain Science, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

IFNG polymorphisms are associated with tuberculosis in Han Chinese pediatric female population - Chen Shen; Wei-Wei Jiao; Wei-Xing Feng; Xi-Rong Wu; Jing Xiao; Qing Miao; Lin Sun; Bin-Bin Wang; Jing Wang; Fang Liu; Dan Shen; A-Dong Shen (Molecular Biology Reports, 2013)

A novel role of ribonuclease inhibitor in regulation of epithelial-to-mesenchymal transition and ILK signaling pathway in bladder cancer cells - Xue Yao; Dan Li; Dong-mei Xiong; Lin Li; Rong Jiang; Jun-xia Chen (Cell and Tissue Research, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

A new sesquiterpene glucoside from Nicotiana rustica L. - Rong Zhou; Dong-Liang Li; Guang-Lin Feng; Guo-You Li (Natural Product Research, 2013)

A Novel Peptide Can Mimic Extracellular Fibrinogen-Binding Protein to Block the Activation of Complement System - Ya-ping Gao; Jie Dong; Xin Zhang; Yu Liu; Qiang Lu; Jian-nan Feng; Xiao-rong Tan; Guang Yang (Cell Biochemistry and Biophysics, 2013)

Curcumin inhibits the metastasis of K1 papillary thyroid cancer cells via modulating E-cadherin and matrix metalloproteinase-9 expression - Chi-Yu Zhang; Li Zhang; Hui-Xin Yu; Jian-Dong Bao; Rong-Rong Lu (Biotechnology Letters, 2013)

Role of Paraoxonase-1 in the Protection of Hydrogen Sulfide-Donating Sildenafil (ACS6) Against Homocysteine-Induced Neurotoxicity - Xiao-Qing Tang; Rong-Qian Chen; Ling Dong; Yan-Kai Ren; Piero Del Soldato; Anna Sparatore; Duan-Fang Liao (Journal of Molecular Neuroscience, 2013)

MicroRNAs-1614-3p gene seed region polymorphisms and association analysis with chicken production traits - Hong Li; Gui-Rong Sun; Ya-Dong Tian; Rui-Li Han; Guo-Xi Li; Xiang-Tao Kang (Journal of Applied Genetics, 2013)

Polymorphisms of UGT1A9 and UGT2B7 influence the pharmacokinetics of mycophenolic acid after a single oral dose in healthy Chinese volunteers - Dong Guo; Liang-Fang Pang; Yang Han; Hong Yang; Guo Wang; Zhi-rong Tan; Wei Zhang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

Decreased PADI4 mRNA Association with Global Hypomethylation in Hepatocellular Carcinoma During HBV Exposure - Changsong Zhang; Lieying Fan; Tingting Fan; Dong Wu; Lu Gao; Yang Ling; Jing Zhu; Rong Li; Lixin Wei (Cell Biochemistry and Biophysics, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Rapid odor perception in rat olfactory bulb by microelectrode array - Jun Zhou; Qi Dong; Liu-jing Zhuang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Oxidative Parameters in the Rat Brain of Chronic Mild Stress Model for Depression: Relation to Anhedonia-Like Responses - Chao Wang; He-ming Wu; Xiao-rong Jing; Qiang Meng; Bei Liu; Hua Zhang; Guo-dong Gao (The Journal of Membrane Biology, 2012)

Magma mingling and chemical diffusion in the Taojiang granitoids in the Hunan Province, China: evidences from petrography, geochronology and geochemistry - Kai-Xing Wang; Pei-Rong Chen; Wei-Feng Chen; Hong-Fei Ling; Kui-Dong Zhao; Zhi-Qiang Yu (Mineralogy and Petrology, 2012)

Establishment of reference mandibular plane for anterior alveolar morphology evaluation using cone beam computed tomography - Rong-yang Wang; Min Han; Hong Liu; Chun-ling Wang; Hong-hong Xian; Lei Zhang; Shi-jie Zhang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Identification and molecular cytology analysis of cold tolerance introgression lines derived from Oryza sativa L. mating with O. rufipogon Griff. - Xiang-Dong Luo; Liang-Fang Dai; Juan-Fang Cao; Shui-Rong Jian; Ya-Ling Chen; Biao-Lin Hu; Jian-Kun Xie (Euphytica, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

RAP2.6L overexpression delays waterlogging induced premature senescence by increasing stomatal closure more than antioxidant enzyme activity - Peiqing Liu; Feng Sun; Rong Gao; Hansong Dong (Plant Molecular Biology, 2012)

Apoplastic and cytoplasmic location of harpin protein Hpa1Xoo plays different roles in H2O2 generation and pathogen resistance in Arabidopsis - Suling Sang; Xiaojie Li; Rong Gao; Zhenzhen You; Beibei Lü; Peiqing Liu; Qixiang Ma; Hansong Dong (Plant Molecular Biology, 2012)

GWAS-linked GAK locus in Parkinson’s disease in Han Chinese and meta-analysis - Nan-Nan Li; Xue-Li Chang; Xue-Ye Mao; Jin-Hong Zhang; Dong-Mei Zhao; Eng-King Tan; Rong Peng (Human Genetics, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Compression technique for compressed sensing hyperspectral images - Chengfu Huo; Rong Zhang; Dong Yin (International Journal of Remote Sensing, 2012)

High mobility group box-1 induces migration of vascular smooth muscle cells via TLR4-dependent PI3K/Akt pathway activation - Jian Yang; Lihua Chen; Jun Yang; Jiawang Ding; Han Rong; Wusong Dong; Xinxin Li (Molecular Biology Reports, 2012)

Population clonal diversity and fine-scale genetic structure in Oryza officinalis (Poaceae) from China, implications for in situ conservation - Yao Zhao; Chengbin Chen; Jun Rong; Shanshan Dong; Hui Liao; Fan Lu; Baorong Lu; Jiakuan Chen; Zhiping Song (Genetic Resources and Crop Evolution, 2012)

Effects of Atorvastatin on Pathological Changes in Brain Tissue and Plasma MMP-9 in Rats with Intracerebral Hemorrhage - Jing-Jing Cui; Dong Wang; Fei Gao; Yue-Rong Li (Cell Biochemistry and Biophysics, 2012)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

Isolation of a buprofezin co-metabolizing strain of Pseudomonas sp. DFS35-4 and identification of the buprofezin transformation pathway - Kai Chen; Xiao-Mei Liu; Rong Li; Yuan Liu; Hai Hu; Shun-Peng Li; Jian-Dong Jiang (Biodegradation, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

LPS pretreatment ameliorates multiple organ injuries and improves survival in a murine model of polymicrobial sepsis - Dong-Wei Shi; Jing Zhang; Hong-Ni Jiang; Chao-Yang Tong; Guo-Rong Gu; Yuan Ji; Hanssa Summah; Jie-Ming Qu (Inflammation Research, 2011)

Chlorothalonil degradation by Ochrobactrum lupini strain TP-D1 and identification of its metabolites - Xiu-Zhen Shi; Rong-Jun Guo; Kazuhiro Takagi; Zuo-Qing Miao; Shi-Dong Li (World Journal of Microbiology and Biotechnology, 2011)

The complete mitochondrial genome of Spilonota lechriaspis Meyrick (Lepidoptera: Tortricidae) - Jin-Liang Zhao; Yan-Yan Zhang; A-Rong Luo; Guo-Fang Jiang; Stephen L. Cameron; Chao-Dong Zhu (Molecular Biology Reports, 2011)

Azoospermia related to a unique karyotype: 45,XY,−13,−19,+der(19)t(13;19)(q12;p13) - Chao Fu; Xin Yun; Yuan Dong; Bai-Yan Wu; Rong-Rong Han; Rui-Zhi Liu (Journal of Applied Genetics, 2011)

Validation and dissection of quantitative trait loci for leaf traits in interval RM4923-RM402 on the short arm of rice chromosome 6 - BO SHEN; WEI-DONG YU; JING-HONG DU; YE-YANG FAN; JI-RONG WU; JIE-YUN ZHUANG (Journal of Genetics, 2011)

QTL mapping for test weight by using F 2:3 population in maize - JUN-QIANG DING; JIN-LIANG MA; CHUN-RONG ZHANG; HUA-FANG DONG; ZHANG-YING XI; ZONG-LIANG XIA; JIAN-YU WU (Journal of Genetics, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

HrpNEa-induced deterrent effect on phloem feeding of the green peach aphid Myzus persicae requires AtGSL5 and AtMYB44 genes in Arabidopsis thaliana - Beibei Lü; Weiwei Sun; Shuping Zhang; Chunling Zhang; Jun Qian; Xiaomeng Wang; Rong Gao; Hansong Dong (Journal of Biosciences, 2011)

Mapping QTLs for grain quality using an introgression line population from a cross between Oryza sativa and O. rufipogon - Ping-Rong Yuan; Hyun-Jung Kim; Qiong-Hua Chen; Hong-Guang Ju; Shi-Dong Ji; Sang-Nag Ahn (Journal of Crop Science and Biotechnology, 2010)

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

A new hexenol glycoside from leaves of Smallanthus sonchifolius - Xiang Zheng; Gai Kuo; Dou De-Qiang; Chen Gui-Rong; Kang Ting-Guo; Shi Yu-Yuan; Li Xing-Tai; Dong Feng (Natural Product Research, 2010)

Diversity and Antimicrobial and Plant-Growth-Promoting Activities of Endophytic Fungi in Dendrobium loddigesii Rolfe - Xiao Mei Chen; Hai Ling Dong; Ke Xing Hu; Zhi Rong Sun; Juan Chen; Shun Xing Guo (Journal of Plant Growth Regulation, 2010)

Chemometrics-based approach to modeling quantitative composition-activity relationships for Radix Tinosporae - Shi-Kai Yan; Zhong-Ying Lin; Wei-Xing Dai; Qi-Rong Shi; Xiao-Hua Liu; Hui-Zi Jin; Wei-Dong Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Hydrolytic Dechlorination of Chlorothalonil by Ochrobactrum sp. CTN-11 Isolated from a Chlorothalonil-Contaminated Soil - Bin Liang; Rong Li; Dong Jiang; Jiquan Sun; Jiguo Qiu; Yanfu Zhao; Shunpeng Li; Jiandong Jiang (Current Microbiology, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

Cytological and RAPD data revealed genetic relationships among nine selected populations of the wild bramble species, Rubus parvifolius and R. coreanus (Rosaceae) - Xiao-rong Wang; Yuan Liu; Bi-feng Zhong; Xiao-li Dong; Qing Chen; Wu-feng Xia; Hanwu Zhang; Hao-ru Tang (Genetic Resources and Crop Evolution, 2010)

Normal Shear Stress and Vascular Smooth Muscle Cells Modulate Migration of Endothelial Cells Through Histone Deacetylase 6 Activation and Tubulin Acetylation - Yan-Hua Wang; Zhi-Qiang Yan; Ying-Xin Qi; Bin-Bin Cheng; Xiao-Dong Wang; Dan Zhao; Bao-Rong Shen; Zong-Lai Jiang (Annals of Biomedical Engineering, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Fate of 15N after combined application of rabbit manure and inorganic N fertilizers in a rice–wheat rotation system - Cheng-Long Wu; Qi-Rong Shen; Jing-Dong Mao; Yang-Chun Xu (Biology and Fertility of Soils, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

QTL dissection of agronomic and domestication traits using introgression lines carrying wild rice (Oryza rufipogon Griff.) segments in cultivated rice (O. sativa L.) background - Ping-Rong Yuan; Hyun-Jung Kim; Qiong-Hua Chen; Hong-Guang Ju; Seung-Joon Lee; Shi-Dong Ji; Sang-Nag Ahn (Journal of Crop Science and Biotechnology, 2009)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Pro-protein convertase-2/carboxypeptidase-E mediated neuropeptide processing of RGC-5 cell after in vitro ischemia - Song-Shan Tang; Juan-Hui Zhang; Huan-Xin Liu; Dong Zhou; Rong Qi (Neuroscience Bulletin, 2009)

Effect of silymarin on the pharmacokinetics of losartan and its active metabolite E-3174 in healthy Chinese volunteers - Yang Han; Dong Guo; Yao Chen; Yu Chen; Zhi-Rong Tan; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus - Xu-Dong Tang; Qiang Xiao; Xiu-Cui Ma; Zeng-Rong Zhu; Chuan-Xi Zhang (Virus Genes, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Responses of Fusarium oxysporum f. sp. niveum to exogenously added sinapic acid in vitro - Hong-sheng Wu; Yang Wang; Wei Bao; Dong-yang Liu; Waseem Raza; Qi-wei Huang; Ze-sheng Mao; Qi-rong Shen (Biology and Fertility of Soils, 2009)

Effects of different nitrogen forms on the growth and cytokinin content in xylem sap of tomato (Lycopersicon esculentum Mill.) seedlings - Ying Lin Lu; Yang Chun Xu; Qi Rong Shen; Cai Xia Dong (Plant and Soil, 2009)

RETRACTED ARTICLE: Pro-protein convertase-2/carboxypeptidase-E mediated neuropeptide processing of RGC-5 cell after in vitro ischemia - Song-Shan Tang; Juan-Hui Zhang; Huan-Xin Liu; Dong Zhou; Rong Qi (Neuroscience Bulletin, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Simulation and analysis of China climate using two-way interactive atmosphere-vegetation model (RIEMS-AVIM) - Rong Gao; Wenjie Dong; Zhigang Wei (Advances in Atmospheric Sciences, 2008)

Isolation and identification of Sclerotinia stem rot causal pathogen in Arabidopsis thaliana - Ai-rong Wang; Wen-wei Lin; Xiao-ting Chen; Guo-dong Lu; Jie Zhou; Zong-hua Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

Allelopathic impact of artificially applied coumarin on Fusarium oxysporum f.sp. niveum - Hong-Sheng Wu; Waseem Raza; Dong-Yang Liu; Cheng-Long Wu; Ze-Shen Mao; Yang-Chun Xu; Qi-Rong Shen (World Journal of Microbiology and Biotechnology, 2008)

Depressive-like behavior in mice recently recovered from motor disorders after 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Sha Ma; Wei Zhou; Zheng Wei; Yu-Xiang Zheng; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2008)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Effect of fungal fusaric acid on the root and leaf physiology of watermelon (Citrullus lanatus) seedlings - Hong-sheng Wu; Xiao-ming Yin; Dong-yang Liu; Ning Ling; Wei Bao; Rong-rong Ying; Yi-yong Zhu; Shi-wei Guo; Qi-rong Shen (Plant and Soil, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

Secretion of malate and citrate from roots is related to high Al-resistance in Lespedeza bicolor - Xiao Ying Dong; Ren Fang Shen; Rong Fu Chen; Zhao Liang Zhu; Jian Feng Ma (Plant and Soil, 2008)

Enhanced expression of phospholipase C 1 (ZmPLC1) improves drought tolerance in transgenic maize - Chun-Rong Wang; Ai-Fang Yang; Gui-Dong Yue; Qiang Gao; Hai-Ying Yin; Ju-Ren Zhang (Planta, 2008)

Identification of defense-related genes in rice responding to challenge by Rhizoctonia solani - Chang-Jiang Zhao; Ai-Rong Wang; Yu-Jun Shi; Liu-Qing Wang; Wen-De Liu; Zong-Hua Wang; Guo-Dong Lu (Theoretical and Applied Genetics, 2008)

Simultaneous biodegradation of methyl parathion and carbofuran by a genetically engineered microorganism constructed by mini-Tn5 transposon - Jiandong Jiang; Ruifu Zhang; Rong Li; Ji-Dong Gu; Shunpeng Li (Biodegradation, 2007)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

Berbamine induces apoptosis in human hepatoma cell line SMMC7721 by loss in mitochondrial transmembrane potential and caspase activation - Guan-yu Wang; Jia-wei Zhang; Qing-hua Lü; Rong-zhen Xu; Qing-hua Dong (Journal of Zhejiang University-SCIENCE B, 2007)

Timing and duration of supergene mineralization at the Xinrong manganese deposit, western Guangdong Province, South China: cryptomelane 40Ar/39Ar dating - Jian-Wei Li; Paulo Vasconcelos; Wei Zhang; Xiao-Dong Deng; Nurdan Duzgoren-Aydin; Dai-Rong Yan; Jian-Qiang Zhang; Ming-An Hu (Mineralium Deposita, 2007)

Phenolic constituents from the rhizomes of Gastrodia elata - Xiao-Dong Yang; Jie Zhu; Rong Yang; Jing-Ping Liu; Liang Li; Hong-Bin Zhang (Natural Product Research, 2007)

Study of Resistin gene expression in peripheral blood mononuclear cell and its gene polymorphism in a small range population - Yun-mei Yang; Zhe-rong Xu; Ling-jiao Wu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Adaptor FADD is recruited by RTN3/HAP in ER-bound signaling complexes - Rong Xiang; Yingle Liu; Lei Zhu; Wei Dong; Yipeng Qi (Apoptosis, 2006)

Glucosamine sulfate–induced apoptosis in chronic myelogenous leukemia K562 cells is associated with translocation of cathepsin D and downregulation of Bcl-xL - Zhe Wang; Rong Liang; Gao-Sheng Huang; Ying Piao; Yong-Qing Zhang; Ai-Qin Wang; Bao-Xia Dong; Ji-Liang Feng; Guo-Rong Yang; Ying Guo (Apoptosis, 2006)

Control of Late Blight (Phytophthora capsici ) in Pepper Plant with a Compost Containing Multitude of Chitinase-producing Bacteria - Dong Hyun Chae; Rong De Jin; Hoon Hwangbo; Yong Woong Kim; Yong Cheol Kim; Ro Dong Park; Hari B. Krishnan; Kil Yong Kim (BioControl, 2006)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Characterization of Recombinant Human Cardiac KCNQ1/KCNE1 Channels (I Ks) Stably Expressed in HEK 293 Cells - Ming-Qing Dong; Chu-Pak Lau; Zhan Gao; Gea-Ny Tseng; Gui-Rong Li (The Journal of Membrane Biology, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Status, causes and combating suggestions of sandy desertification in qinghai-tibet plateau - Yi-hua Liu; Guang-rong Dong; Sen Li; Yu-xiang Dong (Chinese Geographical Science, 2005)

Use of fluorometry for determination of skim milk powder adulteration in fresh milk - Rong-fa Guan; Dong-hong Liu; Xing-qian Ye; Kai Yang (Journal of Zhejiang University-SCIENCE B, 2005)

Ovipositor length of threeApocrypta species: Effect on oviposition behavior and correlation with syconial thickness - Wen-Quan Zhen; Da-Wei Huang; Jin-Hua Xiao; Da-Rong Yang; Chao-Dong Zhu; Hui Xiao (Phytoparasitica, 2005)

Environmental evolution of ordos desert in china since 1.1Ma B.P. as indicated by Yulin stratigraphical section and its grain-size analysis results - Bao-sheng Li; Shang-yu Gao; Guang-rong Dong; He-ling Jin (Chinese Geographical Science, 2005)

Impact of the anomalous thawing in the Tibetan Plateau on summer precipitation in China and its mechanism - Gao Rong; Wei Zhigang; Dong Wenjie; Zhong Hailing (Advances in Atmospheric Sciences, 2005)

Residents’ attitudes to tourism development in ancient village resorts - Li Wang; Lin Lu; Shi-rong Tong; Song Lu; Zhao Yang; Yong Wang; Dong-dong Liang (Chinese Geographical Science, 2004)

Effects of Organic Acids, o-Phenylenediamine and Pyrocatechol on Cadmium Adsorption and Desorption in Soil - Zhou Dong-Mei; Chen Huai-Man; Wang Shen-Qiang; Zheng Chun-Rong (Water, Air, & Soil Pollution, 2003)

Application of geographical parameter database to establishment of unit population database - Chun Dong; Rong Zhao; Ji-ping Liu; Gui-xin Wang; Xi-zhi Wu (Chinese Geographical Science, 2003)

Solvent assistance in regiospecific disulfide formation in dimethylsulfoxide - James P. Tam; Xiang Chao Dong; Cui Rong Wu (International Journal of Peptide Research and Therapeutics, 1999)